Sintered body, sintered body manufacturing method, powder, and temporarily sintered body
Patent Information
- Application Number
- JP2023029258
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-28
- Filing Date
- 2023-02-28
- Publication Date
- 2026-10-16
AI Technical Summary
Existing zirconia sintered bodies, particularly those containing yttria and ceria, exhibit high dynamic strength but lack sufficient static strength, making them inadequate for applications requiring both high dynamic and static strength, such as decorative parts and exterior members.
Incorporating stabilizing elements like neodymium, gadolinium, ytterbium, and samarium, along with yttrium, into zirconia sintered bodies, with specific crystal grain sizes and compositions, to enhance both dynamic and static strength.
The resulting sintered bodies demonstrate improved static and dynamic strength, enabling their use in decorative and structural applications by preventing breakage from external impacts.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to a sintered body having high impact resistance and mainly composed of zirconia, a method for manufacturing a sintered body, a powder, and a calcined body. [Background technology]
[0002] Sintered bodies with zirconia as a matrix (hereinafter also referred to as "zirconia sintered bodies") are being considered for decorative applications in addition to conventional applications requiring strength, such as grinding media and structural materials, including decorative parts for watches, portable electronic devices, automobiles, and home appliances. Sintered bodies used for decorative applications require high strength and toughness to prevent fracture due to external impacts. Various sintered bodies possessing high strength and toughness have been reported to date as highly reliable materials.
[0003] In recent years, sintered bodies have been reported that, in addition to their high strength and toughness, also exhibit improved fracture resistance when subjected to impacts closer to those of practical use (Patent Document 1).
[0004] Patent Document 1 reports a sintered body obtained by sintering a powder mixture containing 3.4 to 5.0 mol% ceria and 0.7 to 1.2 mol% yttria, along with alumina powder. This sintered body is reported to exhibit high impact resistance, i.e., dynamic strength, by forming impact marks due to plastic deformation in response to dynamic loading from a ball drop test. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2021-91601 [Overview of the project] [Problems that the invention aims to solve]
[0006] From the perspective of practical application in exterior components and the like, sintered bodies are required to have high static strength in addition to high dynamic strength. However, the sintered body described in Patent Document 1 has not been reported to have high static strength.
[0007] This disclosure aims to provide at least one of a sintered body having high dynamic and static strength, a method for manufacturing the same, a powder, and a calcined body. [Means for solving the problem]
[0008] The inventors investigated the static strength, particularly the bending strength, of zirconia sintered bodies with high dynamic strength. As a result, they noted that while the solid solution of yttrium and cerium described in Patent Document 1 significantly improved dynamic strength, the improvement in static strength was limited. Furthermore, they found that, compared to the improvement in static strength due to the solid solution of yttrium and cerium, a zirconia sintered body possessing both high dynamic and static strength could be obtained by solid solution of stabilizing elements other than the combination of yttrium and cerium.
[0009] In other words, the present invention is as claimed, and the gist of this disclosure is as follows. [1] A sintered zirconia body containing a stabilizing element, wherein the stabilizing element contains at least one rare earth element other than yttrium, has an average grain size of 0.05 μm or more and 0.75 μm or less, and has a region that undergoes plastic deformation. [2] The sintered body according to [1], wherein the content of the stabilizing element is 0.1 mol% or more and less than 3.0 mol%. [3] The sintered body according to [1] or [2], wherein the rare earth element comprises at least one selected from the group consisting of neodymium, gadolinium, ytterbium, holmium, and samarium. [4] The sintered body according to any one of [1] to [3], further comprising the stabilizing element yttrium. [5] The sintered body according to [1] to [4], wherein the yttrium content is 0 mol% or more and 1.2 mol% or less. [6] A sintered body according to any one of [1] to [5], comprising alumina. [7] The sintered body according to [6], wherein the alumina content is 0.1% by mass or more and 30% by mass or less. [8] Zirconia powder containing a stabilizing element and having a monoclinic fraction of more than 70%, wherein the stabilizing element is at least one rare earth element other than yttrium. [9] The powder according to [8], wherein the content of the rare earth element is 0.1 mol% or more and less than 3.0 mol%.
[10] The powder according to [8] or [9], wherein the rare earth element comprises at least one selected from the group consisting of neodymium, gadolinium, ytterbium, holmium, and samarium.
[11] The powder according to any one of [8] to
[10] , further comprising the stabilizing element yttrium.
[12] The powder according to [8] to
[11] , wherein the yttrium content is 0 mol% or more and 1.2 mol% or less.
[13] A powder according to any one of [8] to
[12] , wherein the crystallite size of the monoclinic zirconia is greater than 15 nm and less than or equal to 80 nm.
[14] BET specific surface area is 8m 2 / g or more 40m 2 Zirconia powder as described in any one of [8] to
[13] , which is less than / g.
[15] A powder containing alumina, as described in any one of [8] to
[14] .
[16] The powder according to
[15] , wherein the alumina content is 0.1% by mass or more and 30% by mass or less.
[17] A method for producing a sintered body by sintering any one of the powders described in [8] to
[16] above.
[18] A calcined body containing zirconia with a monoclinic fraction of more than 70% and containing a stabilizing element, wherein the stabilizing element is at least one rare earth element other than yttrium. [Effects of the Invention]
[0010] This disclosure makes it possible to provide at least one of a sintered body having high dynamic and static strength, a method for manufacturing a sintered body, a powder, and a calcined body. [Brief explanation of the drawing]
[0011] [Figure 1] A schematic diagram showing a ball drop test using a DuPont ball drop test machine. [Figure 2] A schematic diagram showing an example of the impact point (formation of a recess) after a ball drop test. [Figure 3] A schematic diagram showing an example of the area near the impact point after a ball drop test on a conventional sintered body. [Figure 4] A schematic diagram showing an example of the arrangement of measurement samples in a ball-fall test. [Figure 5] A schematic diagram showing a method for measuring the depth of impact marks. [Figure 6] A schematic diagram showing an example of the type of failure observed in a ball drop test: (a) state where failure has occurred, (b) state where failure has not occurred. [Figure 7] Appearance of the sintered body of Example 11 after the ball drop test [Figure 8] Appearance of the Vickers indentation of the sintered body of Example 4 after Vickers hardness measurement. [Figure 9] Raman line mapping results near the Vickers indentation of the sintered body of Example 4 after Vickers hardness measurement. [Modes for carrying out the invention]
[0012] The sintered body and powder of this disclosure will be described below with reference to an example of an embodiment.
[0013] The terms used in this embodiment are as follows:
[0014] "Monoclinic ratio" and "tetragonal ratio" are the proportions of monoclinic and tetragonal crystals in the zirconia crystal phase, respectively. Using powder X-ray diffraction (hereinafter also referred to as "XRD") patterns, the monoclinic ratio can be determined from the following equation (1), and the tetragonal ratio from the following equation (2).
[0015] f m ={I m (111)+I m (11 - 1)} / [I m (111)+I m (11 - 1)+I t,c (111)]×100 (1) f t =I t ((111)), / [I m (111)+I m (11 - 1)+I t,c (111)]×100 (2) In equations (1) and (2), f m is the monoclinic ratio (%), f t is the tetragonal ratio (%), I m (111) and I m (11 - 1) are, respectively, the integrated intensities of the XRD peaks corresponding to the (111) and (11 - 1) planes of the monoclinic crystal, and I t,c (111) is the sum of the integrated intensities of the XRD peaks corresponding to the (111) plane of the tetragonal crystal and the (111) plane of the cubic crystal. [[ID=4३]] [[ID=५४]]
[0016] [[ID=५५]] [[ID=५६]]The following conditions are listed as the measurement conditions. [[ID=५७]] [[ID=५८]]
[0017] [[ID=५९]] [[ID=६०]]X - ray source: CuKα ray (λ = 1.5418 Å)[[ID=६१]] [[ID=६२]]Tube voltage: 45 kV[[ID=६३]] [[ID=६४]]Tube current: 40 mA[[ID=६५]] [[ID=६६]]Measurement mode: continuous scan[[ID=६७]] [[ID=६८]]Scan speed: 4° / min[[ID=६९]] [[ID=७०]]Step width: 0.02°[[ID=७१]] [[ID=७२]]Measurement range: 2θ = 26° or more and 33° or less [[ID=७३]] [[ID=७४]]Goniometer: radius 185 mm[[ID=७५]] [[ID=७६]]The "crystallite diameter of the monoclinic crystal" of zirconia (hereinafter also referred to as "D[[ID=७७]] m [[ID=७८]]") is a value obtained from the XRD pattern of the powder using the following equation (3), and the "crystallite diameter of the tetragonal crystal" (hereinafter also referred to as "D[[ID=७९]] t [[ID=८०]]") is a value obtained from the XRD pattern of the powder using the following equation (4). It should be noted that there may be some errors in the original text, such as the lack of closing parentheses in some expressions. The translation has been made as accurately as possible based on the existing text. D m =κλ / (βcosθ m ) (3) D t =κλ / (βcosθ t ) (4) In equations (3) and (4), D m D is the crystallite size (nm) of the monoclinic crystal. t θ is the crystallite size of a tetragonal crystal (nm), κ is the Scherrer constant (κ=1), λ is the wavelength of the light source used for the XRD measurement (nm), β is the full width at half maximum (°) after correcting for mechanical spreading using quartz sand (manufactured by Wako Pure Chemical Industries, Ltd.) with a grain size of 25 μm to 90 μm, θ m θ is the Bragg angle (°) of the reflection corresponding to the (11-1) plane of the monoclinic crystal in XRD measurements. t λ is the Bragg angle (°) of reflection corresponding to the (111) plane of a tetragonal crystal in XRD measurements. When CuKα radiation is used as the light source for XRD measurements, λ is 0.15418 nm.
[0018] The "BET specific surface area" is a value determined by the BET single-point method, using nitrogen (N2) as the adsorbent, in accordance with JIS R 1626-1996.
[0019] "Average grain size" is the average diameter based on the number of zirconia crystal grains constituting the sintered body. It is determined by performing image analysis on the SEM observation image obtained after heat treatment of a mirror-polished sintered body using a scanning electron microscope (hereinafter also referred to as "SEM").
[0020] SEM observation can be performed using a general scanning electron microscope (e.g., JSM-IT500LA, manufactured by JEOL Ltd.). The SEM observation should be performed by setting the observation magnification appropriately so that the number of crystal grains to be image-analyzed (crystal grains in which the grain boundaries are observed without interruption in the SEM observation image (described later)) is 150 ± 50. In order to suppress the variation in observed crystal grains due to differences in the SEM observation area, it is preferable to obtain SEM observation images such that the total number of crystal grains observed by 2 or more, preferably 3 to 5 or less, SEM observation images equals the number of crystal grains mentioned above. The following conditions can be exemplified as conditions for SEM observation.
[0021] Acceleration voltage: 5~15kV Observation magnification: 5000x to 40000x Image analysis of SEM observations can be performed using image analysis software (for example, Mac-View Ver. 5, manufactured by MOUNTECH). Specifically, crystal grains in which grain boundaries are observed without interruption in the SEM observation are extracted, and the area [μm²] of each extracted crystal grain is calculated. 2 The area is calculated. From the calculated area, the diameter [μm] of a circle with an equal area is converted, and the resulting diameter (Heywood diameter; hereinafter also called "equivalent circle diameter") can be considered as the grain size of the crystal grains. The average value of the equivalent circle diameters of the extracted crystal grains can be used as the average grain size of the sintered body.
[0022] Furthermore, because the contrast of grain boundaries is difficult to observe in mirror-polished sintered bodies, heat treatment must be performed within a range that does not change the grain size.
[0023] Conditions for heat treatment of a sintered body include, for example, holding it at a temperature 50°C or more lower than the sintering temperature for 0.1 hours or more, and the following conditions are examples.
[0024] Heat treatment temperature: 1100℃ to 1500℃ Heat treatment time: 0.1 hours or more, or 1.0 hour or less The sintered body of this disclosure will be described below with reference to an example of an embodiment.
[0025] (Plastic deformation region) The sintered body of this embodiment has regions that undergo plastic deformation. These regions include, for example, areas where impact marks are formed when an impact force is applied. In this embodiment, "plastic deformation" refers to deformation of the sintered body caused by the application of an external force, and which remains in the sintered body after the external force is removed. Therefore, plastic deformation differs from deformation where no deformation remains after the removal of the external force (so-called elastic deformation), and from fracture due to the occurrence and propagation of defects such as cracks without deformation of the sintered body (so-called brittle fracture). Furthermore, the plastic deformation in this embodiment differs from deformation due to the so-called superplastic phenomenon, which occurs when deformation is applied at a constant strain rate in a high-temperature range (for example, a temperature range of 800°C or higher) due to continuous grain boundary sliding. One reason why the impact resistance of the sintered body of this embodiment is improved, that is, why the impact resistance is enhanced, is thought to be that the regions that undergo plastic deformation, such as areas where impact marks are formed (hereinafter also referred to as "plastic deformation regions"), exhibit a function of absorbing and dispersing the energy transmitted by the applied impact force. This suggests that, when an impact force is applied, plastic deformation occurs at least before brittle fracture occurs, thereby suppressing the occurrence of brittle fracture and improving impact resistance.
[0026] The sintered body of this embodiment only needs to have a plastic deformation region in at least a part of the sintered body (i.e., it only needs to be a sintered body having a plastic deformation region), but it may mainly consist of a plastic deformation region, or it may be a sintered body consisting mainly of a plastic deformation region.
[0027] "Impact force" is a force that transmits energy to a sintered body, and is particularly a dynamic external force, preferably an external force that exceeds the fracture resistance of the sintered body, more preferably a dynamic external force that exceeds the fracture resistance of the sintered body, and even more precisely, a dynamic external force that exerts elastic energy on the sintered body.
[0028] "An impact force is applied" means that energy is added to at least a part of the sintered body. Examples include the sintered body coming into contact with the ground when it falls, or an object falling on it, or any other instance where energy is dynamically added to the sintered body through contact with an object.
[0029] An "impact mark" is a trace left on a sintered body where an impact force has been applied, preferably a trace formed on the sintered body by the application of an impact force. In other words, an impact mark is a trace left on the sintered body where plastic deformation has occurred, and is a trace of plastic deformation that occurred prior to fracture. Specific examples of impact marks include recesses, uneven surfaces, recesses, and recesses along the direction in which the impact force was applied, in the impact point (described later).
[0030] In this embodiment, whether or not a sintered body has a plastic deformation region can be confirmed by applying an impact force (for example, a dynamic external force that causes the sintered body to fracture) to the sintered body in any way. For example, by applying an impact force to a sintered body and confirming the formation of impact marks, such as depressions or uneven areas, which are traces of plastic deformation (especially traces of deformation that occurred prior to fracture), the presence of a plastic deformation region in the sintered body can be confirmed. In the sintered body of this embodiment, the impact marks are formed due to plastic deformation, but may also include defects based on brittle fracture, such as cracks, that occur afterward (after the formation of the impact marks). On the other hand, if, after the application of the impact force, only defects based on brittle fracture, such as cracks, are present (i.e., only defects are confirmed without the formation of impact marks due to plastic deformation), or if only deformation originating from fracture, such as Hertz fracture, is present (i.e., only deformation formed by the progression of fracture such as the first crack is confirmed), it can be determined that the sintered body does not have a plastic deformation region.
[0031] A preferred method for confirming the existence of a plastic deformation region is, for example, a drop ball test (hereinafter also simply referred to as the "drop ball test") using a DuPont drop ball tester conforming to JIS K 5600 5-3, in which a 300g drop weight is dropped from a height of 200mm at room temperature.
[0032] Figure 1 is a schematic diagram showing a fall ball test using a DuPont fall ball test machine. As shown in Figure 1, in the fall ball test, the sample to be measured (101) has protective tape (107) attached to its back surface and is placed on the cylindrical sample stand (106) of the fall ball test machine, and is fixed to the sample stand by attaching fixing tape (105) to its side. The drop weight consists of a weight (104) and a punch (102), with the punch (102) placed on the surface of the sample to be measured (101). The fall ball test can be performed by dropping the weight (104) from the punch from a height corresponding to the drop height (the height corresponding to the double arrow in Figure 1; 200 mm). The punch (102) has a cylindrical shape with a spherical (hemispherical) tip. By dropping the weight (104) along the guides (103a, 103b) of the DuPont ball drop test machine, a desired impact force can be applied to the measurement sample (101) via the striking die (102).
[0033] Figure 2 is a schematic diagram showing the appearance of the sintered body of this embodiment after a ball drop test. As shown in Figure 2, it can be confirmed that an impact mark was formed in the region where the impact force from the dropped weight (striking mold) was applied (hereinafter also referred to as the "impact point") of the sintered body of this embodiment during the ball drop test. The impact mark in Figure 2 shows a state in which a recess has been formed near the impact point, and it can be visually confirmed that there is a plastic deformation region. Although not shown, there may be defects based on brittle fracture such as cracks near the recess. In contrast, Figure 3 is a schematic diagram showing the appearance of a conventional sintered body after a ball drop test. As shown in Figure 3, in the conventional sintered body, the formation of an impact mark at the impact point cannot be confirmed, and only defects based on brittle fracture such as cracks have occurred.
[0034] The presence or absence of a plastic deformation region can be confirmed by at least one of the following: visual inspection and / or observation with an optical microscope, or by visual inspection alone. Examples of observation magnifications for optical microscope observation include 1 to 100 times, preferably 10 to 50 times.
[0035] Although not shown in the illustration, conventional sintered bodies with high fracture toughness show no change in appearance before and after the ball drop test, and no impact marks can be observed. On the other hand, in sintered bodies with a plastic deformation region, plastic deformation occurs prior to brittle fracture. Therefore, if impact marks cannot be observed, the presence or absence of a plastic deformation region can be confirmed by repeatedly performing the ball drop test with increasing drop height until impact marks can be observed, and by confirming the formation of impact marks such as depressions.
[0036] In order to evaluate whether or not there is a plastic deformation region that provides acceptable impact resistance for decorative parts such as exterior materials for watches and portable electronic devices, it is preferable in this embodiment to check for the presence or absence of a plastic deformation region by a drop test in which a 300g drop weight is dropped from a height of 200mm.
[0037] The ball drop test in this embodiment can be performed at room temperature (20-30°C) using a DuPont ball drop tester conforming to JIS K 5600 5-3. The following conditions can be used for the ball drop test.
[0038] Dropping weight: (Shape) A cylindrical mold with a spherical tip with a radius of 6.35 mm. (mass) 300g Drop height: 200mm Measurement sample: A sintered body in the shape of a plate measuring 40 mm in length, 30 mm in width, and 2 mm in thickness, with a surface roughness Ra of 0.02 μm or less on both surfaces. To prevent the sample fragments from scattering, the sample is fixed to the sample stand of the ball-fall test machine and to one surface of the sample (a 40mm x 30mm surface; the main surface) using double-sided tape. After positioning the sample, fixing tape (protective tape) is applied along the vertical direction of the main surface opposite to the surface on which the sample was fixed, thereby securing the sample (Figure 4). The ball-fall test can then be performed on the secured sample.
[0039] The depth of the impact marks formed by the ball drop test can be defined as, for example, the depth of the deepest part of the impact mark [mm] (Figure 2:204) relative to the thickness of the sintered body [mm] (Figure 2:203) being greater than 0% and less than or equal to 3.5%, between 0.05% and 3%, and further between 0.5% and 3%. Note that the depth of the impact mark (recess) (204) in Figure 2 is shown with the depth emphasized.
[0040] In this embodiment, the depth of the impact mark can be measured using a general-purpose laser microscope (e.g., VK-9500 / VK-9510, manufactured by Keyence Corporation) or a contact-type surface profile measuring instrument (e.g., Dektak XTL, manufactured by Bruker). When measuring with a laser microscope, the observation magnification can be 10 to 50 times, and even 20 times, and the laser wavelength can be 408 nm.
[0041] Figure 5 shows a schematic diagram illustrating an example of a method for measuring the depth of an impact mark. The method for measuring the depth of an impact mark is not limited to the method shown below. In this embodiment, the depth of the impact mark is measured by creating line profiles in the X-axis direction (503A), which is the direction of the maximum diameter of the impact mark formed in a substantially circular shape when viewed from above the falling surface, and in the Y-axis direction (503B), which is perpendicular to the X-axis direction and extends into the falling surface. The difference between the height of the falling surface and the height of the impact mark surface, i.e., the depth of the impact mark (504), is measured with respect to the Z-axis direction which is perpendicular to the X-axis and Y-axis. The maximum depth measured along the X-axis direction is taken as L1, and the maximum depth measured along the Y-axis direction is taken as L2. The maximum depths are averaged (=(L1+L2) / 2), and the resulting length can be taken as the depth of the impact mark of the sample. When using a laser microscope, a measurement condition of 0.5 μm / step can be exemplified for measuring the length of the deepest part. Prior to measurement, a standard sample provided with the device (for example, a Si substrate with a pattern engraved on it) with a known pattern length should be measured to adjust the accuracy of the analysis.
[0042] Such line profiles and measurements of the deepest point in the Z-axis direction can be performed using image analysis software included with the laser microscope (for example, software name: VK-H1A9VK ANALYZER Version 3.0.1.0).
[0043] (Sintered body) The sintered body of this embodiment contains a stabilizing element, and the stabilizing element includes at least one rare earth element other than yttrium.
[0044] Stabilizing elements are elements that stabilize zirconia, and examples include rare earth elements. The zirconia contained in the sintered body of this embodiment contains at least one rare earth element other than yttrium (Y) as a stabilizing element. Preferably, the rare earth element is other than cerium (Ce). Preferably, the rare earth element contains at least one selected from the group of neodymium (Nd), samarium (Sm), gadolinium (Gd), ytterbium (Yb), and holmium (Ho), more preferably at least one selected from the group of neodymium, samarium, gadolinium, and ytterbium, and even more preferably at least one selected from the group of neodymium, samarium, and gadolinium. The rare earth elements preferably include neodymium in order to give the sintered body of this embodiment a blue color, preferably samarium in order to give the sintered body of this embodiment a yellow color, preferably gadolinium in order to increase the drop strength of the sintered body of this embodiment, and preferably ytterbium in order to increase the hydrothermal degradation resistance of the sintered body of this embodiment. The zirconia contained in the sintered body of this embodiment may contain two or more of these rare earth elements.
[0045] In the zirconia contained in the sintered body of this embodiment, the stabilizing element may further contain yttrium. That is, the stabilizing element contained in the sintered body of this embodiment is preferably (i) at least one selected from the group consisting of neodymium, samarium, gadolinium, ytterbium, and holmium, or (ii) at least one selected from the group consisting of neodymium, samarium, gadolinium, ytterbium, and holmium, and yttrium.
[0046] The amount of stabilizing elements (hereinafter also referred to as "amount of stabilizing elements") should be such that the zirconia is partially stabilized. The amount of stabilizing elements can be greater than 0 mol%, 0.1 mol% or more, 0.2 mol% or more, 0.5 mol% or more, 1.0 mol% or more, or 1.5 mol% or more in terms of oxide, and less than 3 mol%, 2.5 mol% or less, 2.3 mol% or less, 2.0 mol% or less, or less than 2.0 mol%. For example, the amount of stabilizing elements can be greater than 0 mol% and less than 3 mol%, and more preferably 0.1 mol% or more and less than 3 mol%, with a preference of greater than 0 mol% and 2.5 mol% or less, and more preferably 0.5 mol% or more and 2.0 mol% or less. In this embodiment, the amount of stabilizing elements is the ratio (mol%) of the total amount of stabilizing elements in terms of oxide to the total amount of zirconia and stabilizing elements in terms of oxide.
[0047] For stabilizing elements, the oxide equivalents are as follows: neodymium is Nd2O3, samarium is Sm2O3, gadolinium is Gd2O3, ytterbium is Yb2O3, holmium is Ho2O3, and yttrium is Y2O3.
[0048] In a sintered body containing zirconia that contains at least one of neodymium, samarium, gadolinium, ytterbium, and holmium as a stabilizing element, the content of each stabilizing element (hereinafter, when the stabilizing element is neodymium, the content of each stabilizing element is also referred to as "neodymium content," etc.) is greater than 0 mol%, 0.1 mol% or more, 0.2 mol% or more, 0.5 mol% or more, 1.0 mol% or more, or 1.5 mol% or more, and less than 3.0 mol%, 2.5 mol% or less, 2.3 mol% or less, or 2.0 mol% or less.
[0049] In this embodiment, the content of each stabilizing element is the ratio (mol%) of each stabilizing element in terms of oxides to the total amount of zirconia and the stabilizing elements in terms of oxides.
[0050] In this embodiment, the content of each stabilizing element in the sintered body is arbitrary, as long as the above-mentioned amounts of stabilizing elements are satisfied. Examples of the content of each stabilizing element in the sintered body of this embodiment include a neodymium content of, for example, 0.1 mol% or more, 0.2 mol% or more, or 0.5 mol% or more, and less than 3.0 mol%, and a samarium content of, for example, 0.1 mol% or more, 0.3 mol% or more, or 0.5 mol% or more, and less than 3.0 mol%.
[0051] Furthermore, in the sintered body of this embodiment, the gadolinium content is, for example, 0.3 mol% or more or 0.5 mol% or more, and less than 3.0 mol% or 2.5 mol% or less; the ytterbium content is, for example, 0.1 mol% or more or 0.5 mol% or more, and less than 3.0 mol% or 2.5 mol% or less; and the holmium content is, for example, 0.1 mol% or more or 0.5 mol% or more, and less than 3.0 mol% or 2.5 mol% or less.
[0052] The yttrium content is 0 mol% or more. That is, the sintered body of this embodiment may or may not contain yttrium. The yttrium content of the sintered body of this embodiment may be 0 mol% or more, 0.1 mol% or more, 0.3 mol% or more, or 0.5 mol% or more, and may also be 2.5 mol% or less, 2.0 mol% or less, 1.5 mol% or less, or 1.2 mol% or less.
[0053] It is preferable that the stabilizing elements are solid-dissolved in zirconia, and it is preferable that the sintered body of this embodiment does not contain unsolid-dissolved stabilizing elements. In this embodiment, not containing unsolid-dissolved stabilizing elements means that the XRD pattern of the sintered body does not have an XRD peak of a compound of the stabilizing element.
[0054] The sintered body of this embodiment may contain a pigment component. The pigment component contained in the sintered body refers to a component that has the function of coloring the sintered body. This allows the sintered body to exhibit any color tone different from the original color tone of zirconia. The pigment component contained in the sintered body of this embodiment is at least one of elements other than rare earth elements that have the function of coloring zirconia, and compounds thereof. For example, it is preferably a compound containing a metallic element, and more preferably a transition metal element and compounds containing the same. Specifically, the pigment component is more preferably one or more elements selected from the group of vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), and zinc (Zn), and compounds containing one or more of these, and even more preferably an oxide containing one or more elements selected from the group of manganese, iron, cobalt, nickel, and zinc. As for pigment components, for example, by sintering a mixture of zirconia powder and pigment component powder, coloring elements derived from the pigment component powder or compounds containing those coloring elements may be included as pigment components in the zirconia sintered body.
[0055] The form of the pigment component in the sintered body of this embodiment is arbitrary; the pigment component may be included as particles (second phase particles) or may be solid-dissolved in zirconia.
[0056] The sintered body of this embodiment tends to exhibit plastic deformation more readily the lower the pigment component content. The pigment component content is preferably greater than 0% by mass and at least 0.001% by mass. While the pigment component content is arbitrary as long as the sintered body has a plastic deformation region, examples of pigment component content include 10% by mass or less, less than 7.5% by mass, 5.0% by mass or less, 3.5% by mass or less, and 3.0% by mass or less. If a pigment component is included, its content may be greater than 0% by mass and less than or equal to 10% by mass, 0.001% by mass or more and less than 7.5% by mass, 0.01% by mass or more and less than or equal to 5% by mass, or 0.04% by mass or more and less than or equal to 1% by mass. The pigment component content can be determined as the ratio of the total mass of the pigment component (converted to oxides) to the mass of the sintered body of this embodiment. For example, the oxide equivalent of the pigment component may be CoO for cobalt, Fe2O3 for iron, Mn3O4 for manganese, and ZnO for zinc. Furthermore, when the pigment components form a composite oxide, the content of the pigment components can be determined as the ratio of the total mass of the pigment components, converted to composite oxides, to the mass of the sintered body of this embodiment.
[0057] The sintered body of this embodiment may contain alumina (Al2O3). The sintered body of this embodiment does not need to contain alumina, so the alumina content is 0% by mass or more. If alumina is included, the alumina content is greater than 0% by mass and less than 30% by mass, preferably greater than 0% by mass and 25% by mass or less, and more preferably 0.005% by mass or more and 20% by mass or less. Alternatively, the alumina content may be 0% by mass or more, greater than 0%, 0.005% by mass or more, 0.05% by mass or more, or 0.25% by mass or more, and may also be 30% by mass or less, 25% by mass or less, or 20% by mass or less. It is preferable that the sintered body of this embodiment does not contain alumina in order to easily obtain permeability, and from the viewpoint of easily obtaining a dense sintered body at a relatively low temperature, an alumina content of 0.05% by mass or more is preferable, and it is preferable that the alumina content is 30% by mass or less in order to easily obtain high mechanical properties, such as static strength, of the sintered body of this embodiment. The alumina content can be determined as the mass ratio of aluminum (in Al2O3 equivalent) to the total amount of zirconia, stabilizing elements (in oxide equivalent), pigment components (in oxide equivalent), and aluminum (in Al2O3 equivalent).
[0058] Alumina has a significant impact on the mechanical properties of the sintered body in this embodiment, and has almost no effect on coloring the zirconia. Therefore, in this embodiment, alumina, i.e., aluminum oxide that does not form a composite oxide with metal elements, is not included in the pigment component. ru.
[0059] The sintered body of this embodiment may contain, in addition to alumina, one or more additives selected from the group consisting of silica (SiO2), titania (TiO2), gallium oxide (Ga2O3), germanium oxide (GeO2), niobium oxide (Nb2O5), and thallium oxide (Ta2O5), and further, at least one or more additives selected from the group consisting of silica, titania, gallium oxide, and germanium oxide. By including additives, a sintered body with desired mechanical properties can be obtained. When additives are included, their content may be greater than 0% by mass and less than or equal to 5% by mass, 0.001% by mass and less than 3% by mass, 0.01% by mass and less than or equal to 1% by mass, or 0.05% by mass and less than or equal to 0.5% by mass.
[0060] The sintered body of this embodiment may contain unavoidable impurities such as hafnia (HfO2), but it is preferable that it contains no impurities other than stabilizing elements, zirconia, alumina and pigment components as needed, and unavoidable impurities. In this embodiment, the hafnia content can be calculated by assuming that 2% by mass of the zirconia content is hafnia.
[0061] For example, if the sintered body of this embodiment is a sintered zirconia body containing a composite oxide represented by ABO3 or AB2O4, alumina, and holmium and yttrium as stabilizing elements, respectively, the content of each component can be determined as follows. In the following formula, the ZrO2 term, i.e., the zirconia content, can be calculated by subtracting the content of other components (i.e., pigment components, alumina, and stabilizing elements) determined by compositional analysis from the total amount of the sintered body, and it is not necessary to consider the mass of unavoidable impurities, including 2% by mass of hafnia.
[0062] Pigment component amount [mass %] = {(ABO2 + AB2O4) / (Ho2O3 + Y2O3 + ZrO2 (Al2O3 + ABO3 + AB2O4) × 100 Alumina content [mass %] = {Al2O3 / (Ho2O3+Y2O3+ZrO2 (Al2O3 + ABO3 + AB2O4) × 100 Stabilizing element amount [mol%]={(Ho2O3+Y2O3) / (Ho2O3+Y2O3+ZrO2)}×100 Holmium content [mol%] = {(Ho2O3) / (Ho2O3+Y2O3+ZrO2)}×100 Yttrium content [mol%] = {(Y2O3) / (Ho2O3+Y2O3+ZrO2)}×100 (Density of sintered body) The sintered body of this embodiment preferably has a high density, with a relative density of 95% or more, and more preferably 98% to 100%.
[0063] In this embodiment, the measured density is the value obtained as the mass obtained by mass measurement relative to the volume obtained by the Archimedes method. In this embodiment, the relative density can be obtained from the ratio of the measured density to the true density. In this embodiment, the true density (g / cm³) 3 ) is calculated assuming that, if no additives or pigment components are included, the crystalline phase of the sintered zirconia is entirely tetragonal, and the unit cell volume (cm³) of the zirconia is... 3 The unit cell volume can be determined from the unit cell mass (g) for ). The unit cell volume is obtained from the XRD peak corresponding to the tetragonal (004) plane in the XRD pattern measured under the following conditions (hereinafter referred to as "I t Also called "(004)") and XRD peaks corresponding to the tetragonal (220) plane (hereinafter referred to as "I t Also known as (220). The interplanar spacing can be determined using the 2θ of the peak top and Bragg's equation, and the lattice constant can be calculated from there. The unit cell mass can be determined using the results of the compositional analysis of the sintered body, as the total mass of cations and anions contained in the unit cell.
[0064] If the sintered body of this embodiment contains additives or pigment components, the true density of the sintered body is the true density ρ of the zirconia portion calculated by the method described above. ZrThe true density can be determined using the true densities of the additives and pigment components shown below. That is, the true density of the sintered body is the reciprocal of the sum of the mass percentages of each component contained in the sintered body divided by the true density of each component. For example, in the case of a sintered body containing X mass% alumina and Y mass% iron oxide, the true density ρ th This can be calculated as follows.
[0065] ρ th =100 / [(X / 3.987)+(Y / 5.24)+(100−X−Y) / ρ Zr ] The true densities of the additives and pigment components were as follows:
[0066] Alumina (Al2O3): 3.987 [g / cm³] 3 ] Germanium oxide (GeO2): 4.25 [g / cm³] 3 ] Niobium oxide (Nb2O5): 4.6 [g / cm³] 3 ] Iron oxide (Fe2O3): 5.24 [g / cm³] 3 Nickel oxide (NiO): 6.67 [g / cm³] 3 ] Manganese oxide (Mn3O4): 4.81 [g / cm³] 3 ] Cobalt aluminate (CoAl2O4): 4.29 [g / cm³] 3 ] The average grain size of the sintered body in this embodiment is 0.05 μm or more, specifically 0.10 μm or more or 0.15 μm or more, and also 0.75 μm or less, 0.50 μm or less, or 0.40 μm or less. Having the grain size within this range makes it easier for the sintered body to exhibit high bending strength. Preferred average grain sizes include 0.10 μm or more and 0.40 μm or less, or 0.25 μm or more and 0.40 μm or less.
[0067] The crystalline phase of the zirconia in the sintered body of this embodiment preferably includes at least a tetragonal crystal, and may consist of at least one of a tetragonal crystal and a cubic crystal and a monoclinic crystal.
[0068] In this embodiment, the powder X-ray diffraction pattern of the sintered body can be measured using a general crystallinity analysis X-ray diffractometer (for example, instrument name: Ultima IV, manufactured by RIGAKU).
[0069] The following conditions can be used as measurement conditions.
[0070] Radiation source: CuKα radiation (λ=1.5418Å) Tube voltage: 45kV Tube current: 40mA Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ = 20° to 80° Goniometer: Radius 185mm In the above measurements, the diffraction intensity of the XRD peak corresponding to the (004) plane of the tetragonal crystal was confirmed as the area intensity of the XRD peak with its peak top at 2θ = 72.5 ± 1°, and the diffraction intensity of the XRD peak corresponding to the (220) plane of the tetragonal crystal was confirmed as the area intensity of the XRD peak with its peak top at 2θ = 74 ± 1°.
[0071] The sintered body of this embodiment preferably has a falling ball fracture energy (hereinafter also referred to as "falling ball strength") of 0.5 J or more, and more preferably 0.6 J or more, which can be determined from the following formula. Falling ball strength is one of the indicators of impact resistance, and the higher this value, the higher the impact resistance. Examples of falling ball strength for a sintered body include 5 J or less, 2 J or less, or 1 J or less.
[0072] Falling ball force (J) = Mass of falling weight (g) × Falling height (mm) × Gravitational acceleration (m / s²) 2 ) × 10 -6 The acceleration due to gravity is 9.8 m / s². 2 You can use this.
[0073] The drop strength can be measured using the same method as the drop test described above, except that the drop height is set to any of the heights shown below.
[0074] Falling ball height: 50-500mm Fracture can be determined when the sample is divided into two or more parts (Figure 6(a)). On the other hand, if a crack does not reach from one end to the other (Figure 6(b)), it can be considered that no fracture has occurred. If no fracture occurs in a drop test at a specific drop height, the drop test can be repeated by increasing the drop height by a fixed amount (for example, 50 mm at a time) up to 500 mm, and visual observation can be performed in the same way until fracture occurs. Alternatively, the weight of the drop weight can be changed instead of the drop height, and the drop test can be repeated. For example, if no fracture occurs even when the drop height reaches 500 mm, the mass of the drop weight can be changed from 300 g to 500 g, and the drop test can be repeated at a drop height of 350 to 500 mm to measure higher drop strength.
[0075] The Vickers hardness (GPa) of the sintered body in this embodiment is not particularly limited, but is preferably 8.0 GPa or higher, more preferably 8.5 GPa or higher, and more preferably 9.0 GPa or higher, as it makes the surface of the sintered body less susceptible to scratches. Examples of Vickers hardnesses include 20.0 GPa or less, 17.5 GPa or less, or 15.0 GPa or less. Examples of preferred Vickers hardnesses include 8.0 GPa to 20.0 GPa, 8.5 GPa to 17.5 GPa, or 9.0 GPa to 15.0 GPa.
[0076] In this embodiment, Vickers hardness can be measured by a method conforming to JIS R1610:2003. The following conditions are examples of conditions for measuring Vickers hardness.
[0077] Measurement sample: (Sample thickness) 1.5±0.5mm (Measured surface roughness) Ra ≤ 0.02 μm Measured load: 10 kgf The measurement can be performed using a standard Vickers hardness tester equipped with a diamond square pyramidal indenter (e.g., MV-1, manufactured by Matsuzawa Co., Ltd.). The measurement is performed by statically pressing the indenter into the surface of the sample to form an indentation, and measuring the diagonal length of the indentation using an optical microscope built into the Vickers hardness tester or a general optical microscope (e.g., VHX-7000, manufactured by Keyence Corporation). Using the obtained diagonal length, the Vickers hardness can be calculated from the following formula.
[0078] Hv=F / {d 2 / 2sin(α / 2)} In the above equation, Hv is the Vickers hardness, F is the measured load (10 kgf = 9.80665 N), d is the diagonal length of the indentation (mm), and α is the angle of the indenter (136°).
[0079] As an indicator of the fracture resistance of the sintered body in this embodiment, the fracture toughness value can be exemplified. The fracture toughness value of the sintered body in this embodiment, measured by the SEPB method specified in JIS R 1607 (MPa·m), is an example. 0.5 ) is 5 MPa·m 0.5 6 MPa·m or more 0.5 The above conditions apply, and also to 20 MPa·m 0.5 Below or 15 MPa·m 0.5 The following can be exemplified: 5 MPa·m 0.5 More than 20MPa m 0.5 The following, or 6 MPa·m 0.5 More than 15MPa m 0.5 The following is preferable:
[0080] In this embodiment, the bending strength can be measured by a three-point bending test in accordance with JIS R 1601. The bending strength of the sintered body in this embodiment is 900 MPa or more or 950 MPa or more, and can also be 1500 MPa or less, 1400 MPa or less, or 1250 MPa or less, and is preferably 900 MPa to 1500 MPa, 950 MPa to 1400 MPa, or 950 MPa to 1200 MPa.
[0081] The color tone of the sintered body in this embodiment is arbitrary, but CIE1976(L * a * b * ) L in color space * If a is between 0 and 95, * is -15 or more and 15 or -5 or more and 15, and b * The values are either between -40 and 40 or between -30 and 40.
[0082] Lightness L * and chromaticity a * , b * This can be measured using a general spectrophotometer (e.g., CM-700d, manufactured by Konica Minolta) in accordance with JIS Z 8722. * and chromaticity a * , b * The following conditions are suggested for measurement. It is preferable to perform the measurement using a black board as the background (so-called black background measurement).
[0083] Light source: D-65 light source Viewing angle: 10° Measurement method: SCI For measurement, a disc-shaped sintered body with a diameter of 20 mm and a thickness of 2.7 mm should be used. The surface to be evaluated should be mirror-polished (Ra ≤ 0.02 μm), and the color tone should be evaluated. A diameter of 10 mm is suggested as an effective area for color tone evaluation.
[0084] The shape of the sintered body in this embodiment can be, for example, at least one selected from the group consisting of spherical, substantially spherical, elliptical, disc-shaped, cylindrical, cubic, rectangular parallelepiped, polyhedral, and substantially polyhedral shapes. Furthermore, any shape that achieves the intended purpose, such as various applications, is acceptable.
[0085] The sintered body of this embodiment can be used in applications of conventional sintered bodies, particularly zirconia sintered bodies used for structural materials, optical materials, dental materials, etc., but it can also be used as a component requiring relatively high impact resistance, such as for decorative items, covers for accessories such as watches and casings, and exterior components for portable electronic devices such as mobile phones.
[0086] (powder) The powder of this embodiment is a zirconia powder containing a stabilizing element, with a monoclinic crystallinity exceeding 70%, and the stabilizing element containing at least one rare earth element other than yttrium.
[0087] The powder of this embodiment contains zirconia with a stabilizing element and a monoclinic content exceeding 70%. In other words, the powder of this embodiment contains stabilizing element-containing zirconia whose crystalline phase mainly consists of monoclinic crystals. The powder of this embodiment is a so-called zirconia powder, mainly composed of zirconia.
[0088] The zirconia contained in the powder of this embodiment contains at least one rare earth element other than yttria as a stabilizing element. Preferably, the rare earth element is other than cerium (Ce). Preferably, the rare earth element contains at least one selected from the group consisting of neodymium (Nd), samarium (Sm), gadolinium (Gd), ytterbium (Yb), and holmium (Ho), more preferably at least one selected from the group consisting of neodymium, samarium, gadolinium, and ytterbium, and even more preferably at least one selected from the group consisting of neodymium, samarium, and gadolinium. The rare earth element preferably contains neodymium in that it can give the sintered body obtained from the powder of this embodiment a blue color, preferably samarium in that it can give the sintered body obtained from the powder of this embodiment a yellow color, preferably gadolinium in that it tends to increase the drop strength of the sintered body obtained from the powder of this embodiment, and preferably ytterbium in that it tends to increase the hydrothermal degradation resistance of the sintered body obtained from the powder of this embodiment. The zirconia contained in the powder of this embodiment may contain two or more types of rare earth elements.
[0089] The zirconia contained in the powder of this embodiment may also contain yttrium as a stabilizing element. That is, the stabilizing elements contained in the zirconia contained in the powder of this embodiment may be (i) at least one selected from the group consisting of neodymium, samarium, gadolinium, ytterbium, and holmium, or (ii) at least one selected from the group consisting of neodymium, samarium, gadolinium, ytterbium, and holmium, and yttrium.
[0090] The amount of stabilizing elements in the powder of this embodiment may be the same as the amount in the sintered body obtained by sintering the powder of this embodiment, and may be an amount that partially stabilizes the zirconia. The amount of stabilizing elements may be greater than 0 mol%, 0.1 mol% or more, or 0.5 mol% or more in terms of oxide, and may also be less than 3 mol%, 2.5 mol% or less, 2.0 mol% or less, or less than 2.0 mol%, and may be greater than 0 mol% and less than 3 mol%, preferably greater than 0 mol% and 2.5 mol% or less, and more preferably 1.0 mol% or more and 2.0 mol% or less. In this embodiment, the amount of stabilizing elements is the ratio (mol%) of the total amount of stabilizing elements in terms of oxide to the total amount of zirconia and stabilizing elements in terms of oxide.
[0091] In a powder containing zirconia and at least one of neodymium, samarium, gadolinium, ytterbium, and holmium as a stabilizing element, the content of each stabilizing element is greater than 0 mol%, 0.1 mol% or more, 0.2 mol% or more, 0.3 mol% or more, 0.5 mol% or more, 1.0 mol% or more, or 1.5 mol% or more, and less than 3 mol%, 2.5 mol% or less, 2.3 mol% or less, or 2.0 mol% or less.
[0092] In this embodiment, the content of each stabilizing element is the ratio (mol%) of each stabilizing element in terms of oxides to the total amount of zirconia and the stabilizing elements in terms of oxides.
[0093] In this embodiment, the content of each stabilizing element in the powder is arbitrary, as long as the above-mentioned amounts of stabilizing elements are met. Examples of the content of each stabilizing element in the powder of this embodiment include a neodymium content of, for example, 0.1 mol% or more, 0.2 mol% or more, or 0.5 mol% or more, and less than 3.0 mol%, and a samarium content of, for example, 0.1 mol% or more, 0.3 mol% or more, or 0.5 mol% or more, and less than 3.0 mol%.
[0094] Furthermore, the powder of this embodiment preferably has a gadolinium content of, for example, 0.3 mol% or more or 0.5 mol% or more, and less than 3.0 mol% or 2.5 mol% or less; a ytterbium content of 0.1 mol% or more or 0.5 mol% or more, and less than 3.0 mol% or 2.5 mol% or less; and a holmium content of 0.1 mol% or more or 0.5 mol% or more, and less than 3.0 mol% or 2.5 mol% or less.
[0095] It is preferable that the stabilizing elements are solid-dissolved in zirconia, and it is preferable that the powder of this embodiment does not contain undissolved stabilizing elements.
[0096] The powder of this embodiment may contain a pigment. This causes the sintered body to exhibit a color tone different from that of zirconia. The pigment contained in the powder of this embodiment is at least one of elements other than rare earth elements that have the function of coloring zirconia, and compounds thereof. For example, it is preferable that the pigment is a compound containing a metallic element, and more preferably a compound containing a transition metal element. Specifically, it is more preferable that the pigment is a compound containing one or more elements selected from the group of vanadium, chromium, manganese, iron, cobalt, nickel, copper, and zinc, and even more preferable that it is an oxide containing one or more elements selected from the group of manganese, iron, cobalt, nickel, and zinc.
[0097] The sintered body obtained from the powder of this embodiment is more susceptible to plastic deformation the lower the pigment component content. Therefore, the pigment content in the powder of this embodiment is preferably greater than 0% by mass and at least 0.001% by mass. The pigment content of the powder is arbitrary as long as a sintered body having a plastic deformation region is obtained, but examples of pigment content include 10% by mass or less, less than 7.5% by mass, 5.0% by mass or less, and 3.5% by mass or less. The pigment content can be determined as the ratio of the total mass of the pigment, converted to oxide, to the mass of the powder of this embodiment, converted to oxide. Examples of pigments converted to oxide include cobalt as CoO, iron as Fe2O3, manganese as Mn3O4, and zinc as ZnO. Furthermore, when the pigment component forms a composite oxide, the pigment component content can be determined as the ratio of the total mass of the pigment component, converted to composite oxide, to the mass of the sintered body of this embodiment.
[0098] The powder of this embodiment may contain alumina. The powder of this embodiment does not have to contain alumina, so the alumina content is 0% by mass or more. If alumina is included, the alumina content is greater than 0% by mass and less than 30% by mass, preferably greater than 0% by mass and 25% by mass or less, and more preferably 0.005% by mass or more and 20% by mass or less. Alternatively, the alumina content may be 0% by mass or more, greater than 0%, 0.005% by mass or more, 0.05% by mass or more, or 0.25% by mass or more, and may also be 30% by mass or less, 25% by mass or less, or 20% by mass or less. In terms of the ease with which a sintered body obtained from the powder of this embodiment can be permeable, it is preferable that it does not contain alumina. From the viewpoint of easily obtaining a dense sintered body at a relatively low temperature, it is preferable that the alumina content is 0.05% by mass or more. In terms of the ease with which a sintered body can be obtained, it is preferable that the alumina content is 30% by mass or less, as this tends to improve the mechanical properties of the sintered body, such as static strength. The alumina content can be determined as the mass ratio of aluminum (in Al2O3 equivalent) to the total amount of zirconia, stabilizing elements (in oxide equivalent), and aluminum (in Al2O3 equivalent).
[0099] The powder of this embodiment may contain, in addition to alumina, one or more additives selected from the group consisting of silica, titania, gallium oxide, germanium oxide, niobium oxide, and tantalum oxide, and further, one or more additives selected from the group consisting of silica, titania, gallium oxide, and germanium oxide. By including such additives, a sintered body having desired mechanical properties can be obtained.
[0100] The powder of this embodiment may contain unavoidable impurities such as hafnia. However, it is preferable that it contains no impurities other than stabilizing elements, zirconia, alumina, pigment components as needed, and unavoidable impurities. In this embodiment, the hafnia content can be calculated by assuming that 2% by mass of the zirconia content is hafnia.
[0101] For example, if the sintered body of this embodiment is a sintered zirconia body containing two composite oxides represented by ABO3 and AB2O4 as pigment components, and alumina, and also containing holmium and yttrium as stabilizing elements, the content of each component can be determined as follows. In the following formula, the ZrO2 term, i.e., the zirconia content, can be calculated by subtracting the content of other components (i.e., pigment components, alumina, and stabilizing elements) determined by compositional analysis from the total amount of the sintered body, and unavoidable impurities, including 2% by mass of hafnia, can be included in the zirconia content.
[0102] For example, if the powder of this embodiment is a zirconia powder containing two composite oxides represented by ABO3 and AB2O4 as pigment components, and alumina, and also containing holmium and yttrium as stabilizing elements, the content of each component can be determined as follows. In the following formula, the ZrO2 term, i.e., the zirconia content, can be calculated by subtracting the content of other components (i.e., pigment components, alumina, and stabilizing elements) determined by compositional analysis from the total amount of powder, and unavoidable impurities, including 2% by mass of hafnia, can be included in the zirconia content.
[0103] Pigment component amount [mass %] = {(ABO3 + AB2O4) / (Ho2O3 + Y2O3 + ZrO2 (Al2O3 + ABO3 + AB2O4) × 100 Alumina content [mass %] = {Al2O3 / (Ho2O3+Y2O3+ZrO2 (Al2O3 + ABO3 + AB2O4) × 100 Stabilizing element amount [mol%]={(Ho2O3+Y2O3) / (Ho2O3+Y2O3+ZrO2)}×100 Holmium content [mol%] = {(Ho2O3) / (Ho2O3+Y2O3+ZrO2)}×100 Yttrium content [mol%] = {(Y2O3) / (Ho2O3+Y2O3+ZrO2)}×100 The monoclinic ratio of the zirconia contained in the powder of this embodiment is more than 70%, preferably 75% or more, and more preferably 78% or more. The monoclinic ratio is 100% or less, and if the zirconia contains at least one of tetragonal and cubic crystals, the monoclinic ratio will be less than 100%. Furthermore, the sum of the tetragonal and cubic ratios is less than 30%, preferably 25% or less, and more preferably 22% or less. The sum of the tetragonal and cubic ratios should be 0% or more, meaning that tetragonal and cubic crystals do not necessarily have to be included.
[0104] Crystallite size (D) of monoclinic crystals m The wavelength is greater than 15 nm and less than or equal to 80 nm, preferably between 16 nm and 60 nm, and preferably between 18 nm and 55 nm.
[0105] The powder of this embodiment has a BET specific surface area of 8 m². 2 / g or more 40m 2 Less than / g, 10m 2 / g or more 40m 2 Less than / g, 9m 2 / g or more 35m 2 / g or less, 15m 2 / g or more 35m 2 / g or less, 10m2 / g or more 30m 2 / g or less or 17m 2 / g or more 30m 2 It is preferable that the BET specific surface area is 8 m² or less. 2 / g or more, preferably 10m 2 Having a density of 40m or more makes it possible to obtain a dense sintered body even at a relatively low sintering temperature. 2 A value of less than / g tends to result in lower powder jetting properties.
[0106] The powder in this current form preferably has a median diameter of 0.05 μm or more and 0.3 μm or less, and more preferably 0.1 μm or more and 0.3 μm or less.
[0107] In this embodiment, the powder can be exemplified by having a multimodal volume-particle-size distribution curve, and it is preferable that the volume-particle-size distribution curve has peaks (extreme values) at least for particle sizes of 0.05 μm to 0.2 μm and 0.3 μm to 0.5 μm. Powders with a multimodal volume-particle-size distribution curve, such as a bimodal distribution, tend to have high packing properties during molding. As the density of the resulting molded article tends to be high, the ratio of the peak at particle size 0.3 μm to 0.5 μm to the peak at particle size 0.05 μm to 0.2 μm in the volume-particle-size distribution curve (hereinafter also referred to as the "particle-size peak ratio") is preferably greater than 0 and less than 2.5, more preferably 0.1 to 2.0, and even more preferably 0.2 to 1.8.
[0108] The powder of this embodiment preferably has high moldability. Specifically, when the powder of this embodiment is uniaxially pressed at a pressure of 50±5 MPa and then treated with a cold isostatic press (hereinafter also referred to as "CIP") at a pressure of 196±5 MPa to form a molded body, the relative density of the molded body (hereinafter also referred to as "molded body density") is preferably 49% or more and 56% or less, and more preferably 50% or more and 54% or less.
[0109] The powder of this embodiment can be used as a precursor for calcined or sintered bodies, and is suitable as a raw material powder for components that require relatively high impact resistance, such as decorative items, covers for accessories like watches and casings, and exterior components for portable electronic devices like mobile phones.
[0110] When the powder of this embodiment is used to form a calcined body or a sintered body, it may be molded into a compacted body by molding prior to calcination or sintering. Molding, calcination, and sintering can all be carried out by known methods.
[0111] When the powder of this embodiment is used to form a molded body, the molding can be carried out by known methods, such as at least one selected from the group consisting of uniaxial pressure (powder press) molding, cold isohydrostatic pressing, slip casting, and injection molding.
[0112] To improve shape stability, the molded body may contain a binder. The binder may be any organic binder used for molding ceramics, such as one or more selected from the group consisting of acrylic resin, polyolefin resin, wax, and plasticizer. An example of the binder content is that the proportion of the binder to the volume of the molded body is 25% by volume or more and 65% by volume or less. Alternatively, an example is that the binder content exceeds 0% by mass and is 10% by mass of 100% by mass of the molded body.
[0113] The shape of the molded body can be any shape appropriate to the purpose, taking into account shrinkage due to sintering. Examples include at least one selected from the group consisting of spherical, nearly spherical, elliptical, disc-shaped, cylindrical, cubic, rectangular, polyhedral, and nearly polyhedral shapes.
[0114] Calcination can be performed by heat treatment at a temperature below the sintering temperature of the powder, for example, in an atmospheric atmosphere at a temperature of 600°C to less than 1200°C. For sintering, one or more methods selected from the group of known methods, such as pressure sintering, vacuum sintering, and atmospheric pressure sintering, can be applied. Because it is simple and easy to apply industrially, atmospheric pressure sintering is preferred, and atmospheric pressure sintering in an atmospheric atmosphere at a temperature of 1150°C to 1550°C, more preferably 1200°C to 1500°C, is more preferred.
[0115] (Method for producing the powder) The method for producing the powder of this embodiment will be described below.
[0116] The sintered body of this embodiment can be manufactured using any method as long as it yields a powder that satisfies the above requirements. An example of a method for manufacturing the powder of this embodiment is a manufacturing method that includes the steps of: heat-treating a composition containing a zirconia sol containing monoclinic zirconia with an average sol particle size of 100 nm to 400 nm, and a stabilizing element source, at a temperature of 500°C to 1250°C to obtain calcined powder; and pulverizing the calcined powder.
[0117] A calcined powder, which is a precursor to the powder of this embodiment, is obtained by a process in which a composition containing a zirconia sol containing monoclinic zirconia with an average sol particle size of 100 nm to 400 nm, and a stabilizing element source is heat-treated at 500°C to 1250°C to obtain calcined powder (hereinafter also referred to as the "powder calcination process").
[0118] In the powder calcination process, heat treatment is performed at temperatures between 500°C and 1250°C, and further between 600°C and 1250°C. Heat treatment at temperatures above 600°C yields powder that is easily densified by atmospheric pressure sintering. On the other hand, heat treatment at temperatures below 1250°C yields powder that is easily dispersed by grinding. The heat treatment time varies depending on the heat treatment temperature, but examples include 30 minutes to 10 hours.
[0119] The atmosphere for heat treatment is arbitrary and can be selected from the group consisting of an oxidizing atmosphere, an operating atmosphere, an inert atmosphere, and a vacuum atmosphere. An oxidizing atmosphere is preferred, and an atmospheric atmosphere is more preferred.
[0120] The zirconia sol has an average sol particle size of 100 nm or more, preferably 150 nm or more, and preferably 400 nm or less, and more preferably 350 nm or less or 300 nm or less. The zirconia sol contains monoclinic zirconia, and is preferably a zirconia sol containing crystalline zirconia (hereinafter also referred to as "crystalline zirconia sol"), and more preferably a zirconia sol containing crystalline zirconia whose main phase is monoclinic.
[0121] Because it tends to be easily pulverized, the amount of zirconium element in the zirconia sol (hereinafter also referred to as the "adsorbed zirconium amount"), which can be calculated using the following formula, is preferably 1% by mass or less, and more preferably 0.5% by mass or less.
[0122] W zr = (m / m0) × 100 In the above formula, W zr m is the amount of adsorbed zirconium (mass%). m is the mass (mg) of zirconium in the filtrate obtained by ultrafiltration of a slurry of zirconia sol dispersed in pure water using an ultrafiltration membrane with a fractional molecular weight cutoff of 500 to 3 million, converted to zirconia (ZrO2) equivalent. The amount of zirconium in the filtrate can be measured by ICP analysis. m0 is the mass (mg) of the zirconia sol before ultrafiltration after heat treatment at 1000°C for 2 hours in an atmospheric environment.
[0123] The zirconia sol used in the powder calcination process only needs to have the characteristics described above, and the method of production is arbitrary, with at least one of the neutralization coprecipitation method, hydrothermal synthesis method, and hydrolysis method being examples. In the hydrothermal synthesis method, zirconia sol is obtained by heat-treating the coprecipitation obtained by mixing a zirconium salt with an alkali, etc., in the presence of a solvent at 100 to 200°C. In the hydrolysis method, zirconia sol is obtained by hydrolyzing a zirconium salt by heating it in the presence of a solvent. Thus, the zirconia sol can be exemplified as a zirconia sol obtained by the hydrothermal synthesis method or the hydrolysis method, and it is preferable that the zirconia sol is obtained by the hydrolysis method.
[0124] Zirconium salts are used as precursors in the method for producing zirconia sol. Examples of zirconium salts include one or more selected from the group consisting of zirconium oxychloride, zirconium nitrate, zirconium chloride, and zirconium sulfate, and it is preferable that at least one of zirconium nitrate and zirconium oxychloride be used, with zirconium oxychloride being more preferable.
[0125] The following describes a preferred method for producing zirconia sol, using hydrolysis as an example. The hydrolysis conditions can be any conditions that allow sufficient hydrolysis of the zirconium salt to proceed. For example, an aqueous solution of zirconium salt can be boiled under reflux for 130 to 200 hours. When hydrolysis is performed with an anion concentration in the aqueous solution of zirconium salt between 0.2 mol / L and 0.6 mol / L, and further between 0.3 mol / L and 0.6 mol / L, the average sol particle size tends to increase.
[0126] The stabilizing element source can be any compound containing a stabilizing element, such as neodymium, samarium, gadolinium, ytterbium, and holmium, or a compound containing at least one element selected from the group consisting of neodymium, samarium, gadolinium, ytterbium, and holmium, which are precursors thereof; preferably, a chloride containing at least one element selected from the group consisting of neodymium, samarium, gadolinium, ytterbium, and holmium (hereinafter, the stabilizing element source when the stabilizing element is neodymium, etc., will also be referred to as the "neodymium source," etc.). The powder of this embodiment may further contain a compound containing yttria, or its precursor yttrium, as the stabilizing element source.
[0127] The neodymium source may be at least one of neodia (neodymium oxide) and neodymium compounds that are precursors thereof, and may be one or more selected from the group consisting of neodymium chloride, neodia, and neodymium carbonate, with the preference being at least one of neodymium chloride and neodymium oxide.
[0128] The samarium source may be at least one of samarium oxide (samarium chloride) and a samarium compound that is a precursor thereof, and may be one or more selected from the group consisting of samarium chloride, samarium oxide, and samarium carbonate, with at least one of samarium chloride and samarium oxide being preferred.
[0129] The gadolinium source may be at least one of gadolinium oxide and gadolinium compounds that are precursors thereof, and may be one or more selected from the group consisting of gadolinium chloride, gadolinium oxide, and gadolinium carbonate, with gadolinium chloride and gadolinium oxide being preferred.
[0130] The yttrium source may be at least one of yttria (yttrium oxide) and yttrium compounds that are precursors thereof, and may be one or more selected from the group consisting of yttrium chloride, yttria, and yttrium carbonate, with at least one of yttrium chloride and yttrium oxide being preferred.
[0131] The composition subjected to the powder calcination process may contain the above-mentioned zirconia sol and stabilizing element source, and all or part of the stabilizing element source may be solid-dissolved in the zirconia sol.
[0132] For example, by mixing a zirconium salt with a stabilizing agent source and hydrolyzing it, or by mixing a zirconium salt, a stabilizing element source, and an alkali, etc., to form a coprecipitate, at least a portion of the stabilizing element source becomes more readily soluble in zirconia.
[0133] The composition used in the powder calcination process may contain an alumina source. The alumina source is at least one of alumina and aluminum compounds that are precursors thereof, and examples include one or more selected from the group consisting of alumina, aluminum hydroxide, aluminum nitrate, and aluminum chloride.
[0134] The zirconia sol, stabilizing element source, and alumina source should be mixed together to achieve a composition similar to that of the desired powder.
[0135] The physical properties of the calcined powders are as follows: BET specific surface area is 3m². 2 / g or more 50m 2 Examples include being less than or equal to / g, and having a monoclinic crystallite size of 5 nm to 100 nm.
[0136] In the process of crushing the calcined powder (hereinafter also referred to as the "crushing process"), the calcined powder is crushed. Crushing the calcined powder tends to increase the yield during sintering.
[0137] To obtain a powder with a desired composition, the grinding step may involve grinding a mixed powder of calcined powder, an alumina source, and other additives instead of calcined powder. The alumina source can be the alumina source described above. Other additives can be at least one selected from the group consisting of silica, titania, gallium oxide, germanium oxide, niobium oxide, and tantalum oxide, with germanium oxide and niobium oxide being preferred examples. The other additive source can be at least one of the additive and its precursor.
[0138] Furthermore, for the purpose of coloring the sintered body obtained from the powder of this embodiment, in the grinding step, instead of the calcined powder, a mixed powder of calcined powder and pigment may be ground.
[0139] The pigment source may be at least one of the pigment and its precursor. Examples of pigment precursors include compounds containing elements that have the function of coloring zirconia, for example, compounds containing metal elements are preferred, and examples include one or more selected from the group of metal oxides, hydroxides, oxyhydroxides, carbonates, oxalates, sulfates, acetates, nitrates, chlorides, fluorides, bromides and iodides, and preferably one or more selected from the group of metal oxides, hydroxides, oxyhydroxides and carbonates. Examples of specific pigment precursors include one or more selected from the group of manganese oxide, iron oxide and cobalt oxide.
[0140] The pigment may contain a metal oxide having a perovskite structure (ABO3) or a spinel structure (AB2O4), and may also contain one or more selected from the group consisting of oxides, hydroxides, oxyhydroxides, carbonates, oxalates, sulfates, acetates, nitrates, chlorides, fluorides, bromides, and iodides of each transition metal contained in the metal oxide. The metal oxide having a perovskite structure (ABO3) or a spinel structure (AB2O4) can be obtained by mixing one or more selected from the group consisting of oxides, hydroxides, oxyhydroxides, carbonates, oxalates, sulfates, acetates, nitrates, chlorides, fluorides, bromides, and iodides of each transition metal contained therein and firing in an air atmosphere at 1200°C to 1500°C. The pigment may contain such a composite metal oxide, or it may contain individual oxides of multiple metal elements that constitute the composite metal oxide.
[0141] A commercially available pigment source may be used, and preferred pigment sources include one or more selected from the group consisting of CoAl2O4, Mn3O4, Fe2O3, NiO, and ZnO, and more specifically, CoAl2O4, Mn3O4, Fe2O3, NiO, and ZnO.
[0142] The grinding method is arbitrary and may be at least one of wet grinding or dry grinding, with wet grinding being preferred. Specific examples of wet grinding include one or more selected from the group consisting of ball mills, vibratory mills, and continuous media stirring mills, with ball mills being preferred.
[0143] As for the conditions for grinding with a ball mill, for example, calcined powder and a solvent are mixed to form a slurry in which the mass ratio of calcined powder to the total slurry mass is 30% by mass or more and 60% by mass or less, and this slurry is ground using zirconia balls with a diameter of 1 mm or more and 15 mm or less as the grinding medium for 10 hours or more and 100 hours or less.
[0144] After wet grinding, the material can be dried by any method to obtain a powder. Examples of drying conditions include an air atmosphere and a temperature between 110°C and 130°C.
[0145] In order to improve the handling properties of the powder, in the method for producing a powder of the present embodiment, a step of granulating the powder (hereinafter, also referred to as "granulation step") may be included. Granulation can be carried out by any method, and examples thereof include spray granulation of a slurry obtained by mixing the powder and a solvent. The solvent is at least one of water and alcohol, preferably water. The granulated powder (hereinafter, also referred to as "powder granule") has an average particle diameter of 30 μm or more and 80 μm or less, more preferably 40 μm or more and 70 μm or less, and a bulk density of 1.00 g / cm 3 or more and 1.70 g / cm 3 or less, more preferably 1.10 g / cm 3 or more and 1.65 g / cm 3 or less.
[0146] (Method for producing a sintered body) Next, the method for producing a sintered body of the present embodiment will be described.
[0147] The method for producing a sintered body of the present embodiment is not particularly limited, but the sintered body of the present embodiment can be obtained by a method having at least a step of sintering the powder of the present embodiment (hereinafter, also referred to as "sintering step"). When producing by sintering the powder obtained above, prior to sintering, the above powder may be formed into a formed body (compressed powder body).
[0148] The content of the stabilizing element source in the formed body may be equivalent to the amount of the stabilizing element in the target sintered body.
[0149] The formed body may contain an alumina source. The alumina source is at least one of alumina (Al2O3) and a compound containing aluminum (Al) as its precursor, and examples thereof include one or more selected from the group consisting of aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum hydroxide, and alumina, and alumina is preferred.
[0150] The content of the alumina source in the formed body may be equivalent to the alumina content of the target sintered body.
[0151] The molded body may contain additives other than the alumina source. The additive content in the molded body should be equivalent to the additive content in the target sintered body.
[0152] When using zirconia containing stabilizing elements, the method for incorporating the stabilizing elements into the zirconia is arbitrary. For example, this can be done by mixing hydrated zirconia sol with a source of stabilizing elements equivalent to the desired stabilizing element content, followed by drying, calcination, and washing with water.
[0153] The molded body may contain a pigment component source as needed. The content of the pigment component source in the molded body should be equivalent to the content of the pigment component in the target sintered body. For example, a molded body containing a pigment component source can be obtained by molding a mixed powder obtained by mixing the above powder with a pigment component source.
[0154] The method of mixing the above powder with the pigment component source is arbitrary, preferably at least one of dry mixing and wet mixing, more preferably wet mixing, and even more preferably wet mixing using a ball mill.
[0155] The molding method can be any known molding method capable of forming a compacted powder from a mixed powder, preferably at least one selected from the group consisting of uniaxial compression molding, isotropic compression molding, injection molding, extrusion molding, rolling granulation, and casting molding, more preferably at least one of uniaxial compression molding and isotropic compression molding, and even more preferably at least one of cold isostatic pressing and uniaxial compression molding (powder pressing), with a method of performing cold isostatic pressing after uniaxial compression molding being even more preferable.
[0156] The process may include a step of pre-calcining the molded body to obtain a calcined body prior to sintering (hereinafter also referred to as the "calcination step"). By pre-calcining the molded body, the binder can be removed from the molded body.
[0157] The conditions for the calcination process are arbitrary as long as the sintered body of this embodiment is obtained, but examples include heat treatment in an air atmosphere at 400°C or higher and less than 1100°C. The resulting calcined body contains stabilizing elements and zirconia with a monoclinic ratio of more than 70%, and it is preferable that the stabilizing elements include at least one rare earth element other than yttrium.
[0158] The sintering process involves sintering the molded body or calcined body to obtain a sintered body. The sintering method is arbitrary, and known sintering methods such as atmospheric pressure sintering, pressure sintering, and vacuum sintering can be exemplified. A preferred sintering method is atmospheric pressure sintering, and because it is simple, it is preferable to use only atmospheric pressure sintering. This allows the sintered body of this embodiment to be obtained as a so-called atmospheric pressure sintered body. Atmospheric pressure sintering is a method of sintering by simply heating the molded body (or calcined body) without applying any external force during sintering.
[0159] The conditions for atmospheric pressure sintering are preferably such that the sintering temperature is 1100°C to 1600°C, 1200°C to 1580°C, or 1200°C to 1560°C, and more preferably 1200°C to 1500°C or 1200°C to 1450°C. The sintering atmosphere may be at least one of an air atmosphere or an oxygen atmosphere, with an air atmosphere being preferred.
[0160] The sintering time can be adjusted as appropriate depending on the sintering method, the size and amount of powder (molded body) used for sintering, and the performance of the sintering furnace used, but examples include 0.5 hours to 8 hours. [Examples]
[0161] The present disclosure will be specifically described below with reference to examples. However, the present disclosure is not limited to these examples.
[0162] (Average sol particle size) The average sol particle size of the zirconia sol was measured using a dynamic light scattering particle size distribution measuring device (device name: UPA-UT151, manufactured by Microtrac Bell). As a pretreatment of the sample, a solution containing hydrated zirconia sol was suspended in pure water and stirred for 3 minutes using an ultrasonic homogenizer.
[0163] (monoclinic ratio, tetragonal ratio, D t and D m ) A general X-ray diffractometer (device name: UltimaIV, manufactured by Rigaku) was used to obtain the XRD pattern of the powder sample. The conditions for the XRD measurement are as follows.
[0164] X-ray source: CuKα ray (λ = 1.5418 Å) Tube voltage: 45 kV Tube current: 40 mA Measurement mode: continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ = 26° or more and 33° or less Goniometer: radius 185 mm Using the obtained XRD pattern, the monoclinic ratio, tetragonal ratio, D t and D m were determined according to formulas (1) to (4).
[0165] (BET specific surface area) A general flow-type specific surface area automatic measuring device (device name: FlowSorb III 2305, manufactured by Shimadzu Corporation) and nitrogen as the adsorption gas were used to measure the BET specific surface area of the powder sample. Prior to the measurement, the powder sample was pretreated by degassing in an air atmosphere at 250 °C for 30 minutes.
[0166] (Particle size distribution measurement) Using the HRA mode of a Microtrac particle size distribution meter (device name: MT3000II, manufactured by Microtrac Bell), the volume particle size distribution curve of the powder sample was measured for the median diameter. Prior to the measurement, the powder sample was suspended in pure water and dispersed for 10 minutes using an ultrasonic homogenizer as a pretreatment.
[0167] (Average grain size) The average grain size was determined using the method described above for samples obtained by thermal etching of mirror-polished sintered bodies, using SEM-EDS (instrument name: JSM-IT500LA, JEOL Ltd.) and image analysis software (software name: Mac-View Ver.5, MOUNTECH Inc.). Thermal etching was performed at a temperature 100°C lower than the sintering temperature of the sintered body for 0.5 hours. After thermal etching, the samples were coated with Au using an SEM deposition system (DII-29010SCTR Smart Coater, JEOL Ltd.) and then observed by SEM.
[0168] For the SEM observation images imported into image analysis software, zirconia crystal grains with unbroken grain boundaries were extracted by tracing the grain boundaries of the zirconia crystal grains within the software. After extraction, the area and equivalent diameter of the crystal grains were determined using the image analysis software, and the average crystal grain size was calculated. In sintered bodies containing pigment components or alumina, where the pigment components or alumina precipitate as crystal grains, the SEM observation image includes crystal grains of the pigment components, alumina crystal grains, and zirconia crystal grains. In this case, since the alumina particles and pigment component crystal grains are observed as having a darker color tone compared to zirconia particles and can be detected by SEM-EDS, such crystal grains were excluded, and after extracting 150 ± 50 crystal grains, the area and equivalent diameter of the crystal grains were determined, and the average crystal grain size was calculated.
[0169] (Sintered body density) The measured density of a sintered body sample is the ratio of the volume measured by the Archimedes method to the mass measured by mass dating (g / cm³). 3 The true density (g / cm³) was determined as follows. Prior to the measurement, the mass of the sintered body after drying was measured, and then the sintered body was placed in water and boiled for 1 hour as a pretreatment. 3 ) When the sintered zirconia does not contain pigment components, alumina, or other additives, it is assumed that the crystalline phase of the zirconia is entirely tetragonal, and the unit cell volume (cm³) of the zirconia is... 3The unit cell mass (g) was determined from the unit cell mass (g) for the given material. The unit cell volume was determined from the interplanar spacing using Bragg's formula and the 2θ (2θ = 72.5 ± 1° and 74 ± 1°) of the peak tops of the XRD peaks corresponding to the tetragonal (004) plane and the XRD peak corresponding to the tetragonal (220) plane in the powder X-ray diffraction pattern measured for the sintered body of this embodiment. The conditions for the XRD measurement are as follows. When pigment components, alumina, and other additives are included, the true density of the zirconia portion was calculated using the method described above, and then the true density of the sintered body was calculated using the true density of the pigment components, alumina, and other additives.
[0170] Radiation source: CuKα radiation (λ=1.5418Å) Tube voltage: 45kV Tube current: 40mA Measurement mode: Continuous scan Scan speed: 2° / min Step width: 0.02° Measurement range: 2θ = 72° to 76° Goniometer: Radius 185mm Furthermore, the unit cell mass was determined using the results of the compositional analysis of the sintered body, as the total mass of cations and anions contained in the unit cell. The relative density (%) was calculated from the measured density (ρ) relative to the true density (ρ0), and this was used as the sintered body density.
[0171] (Confirmation of the plastic deformation region) The presence or absence of a plastic deformation region in the sintered body sample was confirmed by a ball-dropping test using a DuPont type ball-dropping test machine (device name: H-50, manufactured by Toyo Seiki Co., Ltd.) conforming to JIS K 5600 5-3. The test conditions are shown below.
[0172] Dropping weight: (Shape) A cylindrical mold with a spherical tip with a radius of 6.35 mm. (Mass) 300g, that is, a 300g weight made of stainless steel, in the shape of a rectangular prism measuring 80mm wide x 20mm thick x 30mm high. Drop height: 200mm Measurement sample: A sintered body in the shape of a plate measuring 40 mm (length) x 30 mm (width) x 2 mm (thickness), with a surface roughness of Ra ≤ 0.02 μm on both surfaces (the 40 mm x 30 mm surface; the main surface). To prevent the sample fragments from scattering, the sample was fixed to the sample stand of the ball-fall test machine and one surface of the sample (a 40mm x 30mm surface) using double-sided tape. After positioning, tape was applied along the vertical direction of the surface opposite the fixed surface of the sample to secure it. The ball-fall test was then conducted by positioning the drop weight so that it fell near the center of the secured sample.
[0173] (Measurement of ball drop strength) Aside from changing the height of the falling ball, the falling ball strength was measured using the same method as in the falling ball test used to confirm the plastic deformation region. Specifically, the condition of the sample after dropping the weight was visually inspected, and the falling ball strength at the height at which fracture occurred in the sample was calculated using the following formula.
[0174] Ball impact force (J) = Mass of falling weight (g) × Height of fall (mm) × Gravitational acceleration (9.8 m / s²) 2 ) × 10 -6 Fracture was determined when the sample was broken into two or more pieces. However, extremely small fragments, such as chipping, that formed while the sample maintained a plate-like shape were not considered fracture. If no fracture occurred in the drop test at a specific drop height, the drop test was repeated by increasing the drop height by 50 mm increments from 50 mm to 500 mm until fracture occurred. If no fracture occurred even at a drop height of 500 mm, the mass of the drop weight was changed from 300 g to 500 g, and then from 500 g to 1 kg, and the drop test was repeated at a drop height of 500 mm. For samples that did not fracture in the drop test at a drop height of 500 mm with a drop weight mass of 1 kg, the drop strength was arbitrarily set to >5 J (greater than 5 J).
[0175] (Vickers hardness) Vickers hardness was measured using a standard Vickers testing machine (device name: MV-1, manufactured by Matsuzawa Co., Ltd.) equipped with a diamond square pyramidal indenter.
[0176] The indenter was statically pressed into the surface of the sample, and the diagonal length of the indentation formed on the sample surface was measured using an optical microscope built into the Vickers tester or a general optical microscope (device name: VHX-7000, manufactured by Keyence Corporation). The Vickers hardness (GPa) was then calculated using the above formula based on the obtained diagonal length.
[0177] The sintered body sample used was a disc-shaped specimen with a diameter of 20 mm and a thickness of 1.8 mm, which was mirror-polished before use.
[0178] (Fracture resistance) The fracture toughness values of the sintered body samples were measured using a method compliant with the SEPB method specified in JIS R 1607.
[0179] (Bending strength) The bending strength of the sintered body sample was measured using a three-point bending test in accordance with JIS R 1601.
[0180] (Color measurement) The color tone of the sintered body sample was measured according to the method specified in JIS Z 8722. A general spectrophotometer (device name: CM-700d, manufactured by Konica Minolta) was used for the measurement, and a black background measurement was performed using a black plate behind the device. The measurement conditions were as follows:
[0181] Light source: D-65 light source Viewing angle: 10° Measurement method: SCI The sintered body sample used was a disc-shaped specimen with a diameter of 20 mm and a thickness of 2.7 mm, which had been mirror-polished. One surface of the sintered body sample was mirror-polished (Ra ≤ 0.02 μm), and this surface was used as the evaluation surface for color tone evaluation. The effective area for color tone evaluation was set to a diameter of 10 mm.
[0182] (Observation of the external appearance near the Vickers indentation) The square-shaped indentations (hereinafter also referred to as "Vickers indentations") that came into contact with the Vickers indenter and reflected the shape of the indenter in the sintered body after Vickers hardness testing were observed using an optical microscope built into the Vickers testing machine or a general optical microscope (device name: VHX-7000, manufactured by Keyence Corporation).
[0183] (Micro-Raman measurement around Vickers indentation) A standard Raman spectrophotometer (model name: NRS-5100, manufactured by JASCO Corporation) was used to photograph Vickers indentations with the optical microscope built into the instrument. Line mapping was performed along the line segment BB', shown as a dashed line in Figure 9. Line segment BB' is 500 μm long, located 150 μm from the center point A of the Vickers indentation, and parallel to one side of the square-shaped Vickers indentation. The center point A of the Vickers indentation is the point where the tip of the indenter made contact, and the midpoint of line segment BB' is point H, located 150 μm from point A. In Figure 9, x [μm] represents the distance from point B on line segment BB'. The mapping conditions were as follows.
[0184] Measurement area: 500μm Measurement interval: 1μm Number of measurement points: 500 points After line mapping, the monoclinic fraction of the sintered body surface was calculated using the following formula.
[0185] V m.r =I m.r / (K×I t.r +I m.r ) Here, V m.r : Monoclinic coefficient, I m.r :179cm -1 and 189cm -1 The sum of Raman peak intensities in I t.r :149cm -1 The Raman peak intensity value is shown, and K is the sensitivity correction factor (2.2).
[0186] Example 1 An aqueous solution of zirconium oxychloride with zirconium concentration and chloride ion concentration of 0.4 mol / L each was hydrolyzed. The aqueous solution after hydrolysis was ultrafiltered using an ultrafiltration membrane (molecular weight cutoff: 6000) to obtain a zirconia sol with an average sol particle size of 250 nm. zr The levels were below the detection limit (0.01 mass% or less).
[0187] 2500 g of ultrafiltered zirconia sol aqueous solution was mixed with gadolinium chloride hexahydrate to a gadolinium content of 1.6 mol%, and then coprecipitation was induced by adding ammonia aqueous solution to obtain a precipitate. The obtained precipitate was washed with pure water and dried in an air atmosphere, and then calcined in an air atmosphere at a calcination temperature of 1000°C for 2 hours to obtain calcined powder. The BET specific surface area of the obtained calcined powder was 13.6 m². 2 The crystallite size for the monoclinic crystal was 15 nm.
[0188] The calcined powder was mixed with pure water to form a slurry, which was then ground for 24 hours in a ball mill using 2 mm diameter zirconia balls as the grinding medium. After grinding, the slurry was dried in an air atmosphere at 110°C, and coarse particles with an aggregate diameter exceeding 180 μm were removed by sieving to obtain a powder consisting of gadolinium-containing zirconia with a gadolinium content of 1.6 mol%, which was used as the powder for this example. The zirconia crystal phase in the powder of this example consisted of monoclinic and tetragonal phases. The median diameter was 0.21 μm, and the volume-to-particle-size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.36 μm, with a particle size peak ratio of 0.90.
[0189] The powder of this embodiment was subjected to uniaxial compression molding at a pressure of 50 MPa and CIP treatment at a pressure of 196 MPa to form a molded body. The obtained molded body was then subjected to atmospheric pressure sintering in an air atmosphere at a sintering temperature of 1350°C for 2 hours to obtain a sintered body.
[0190] Example 2 A zirconia powder containing 0.25% by mass of alumina and 1.6 mol% of gadolinium was obtained in the same manner as in Example 1, except that the calcined powder and alumina sol were mixed with pure water to form a slurry so that the alumina content was 0.25% by mass. The zirconia crystal phase in the powder of this example consisted of monoclinic or tetragonal phases, i.e., monoclinic and tetragonal. The median diameter was 0.22 μm, and the volume-to-particle-size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.36 μm, with a particle-size peak ratio of 1.01.
[0191] Molded bodies and sintered bodies were obtained in the same manner as in Example 1, except that the powder in question was used.
[0192] Example 3 The powder of this example was obtained in the same manner as in Example 1, except that gadolinium chloride hexahydrate was added to the ultrafiltered zirconia sol aqueous solution so that the gadolinia content was 2.0 mol%, and that calcined powder, alumina sol, and pure water were mixed to form a slurry so that the alumina content was 0.25 mass%. The zirconia crystal phase in the powder of this example was monoclinic or tetragonal, i.e., it consisted of monoclinic and tetragonal phases. The median diameter was 0.16 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.35 μm, with a particle size peak ratio of 0.72.
[0193] Molded bodies and sintered bodies were obtained in the same manner as in Example 1, except that the powder in question was used and the sintering temperature was set to 1450°C.
[0194] Example 4 The powder of this example was obtained in the same manner as in Example 1, except that the calcined powders of Example 1 and Example 3 were mixed so that the gadolinium content was 1.8 mol%, and the mixed calcined powder and alumina sol were mixed with pure water to form a slurry so that the alumina content was 0.25 mass%. The zirconia crystal phase in the powder of this example was monoclinic or tetragonal, i.e., it consisted of monoclinic and tetragonal phases. The median diameter was 0.15 μm, and the volume particle size distribution curve was a bimodal distribution with peaks at particle sizes of 0.14 μm and 0.35 μm, with a particle size peak ratio of 0.60. Molded bodies and sintered bodies were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was 1400°C.
[0195] Example 5 The powder of this example was obtained in the same manner as in Example 1, except that the calcined powder and alumina powder were mixed with pure water to form a slurry so that the alumina content was 5% by mass, and the powder consisted of zirconia containing 5% by mass of alumina and 1.6 mol% of gadolinium. The crystalline phase of the zirconia in the powder of this example was monoclinic or tetragonal, that is, it consisted of monoclinic and tetragonal phases. Molded bodies and sintered bodies were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was 1400°C.
[0196] Example 6 The powder of this example was obtained in the same manner as in Example 1, except that the calcined powder and alumina powder were mixed with pure water to form a slurry so that the alumina content was 10% by mass, and the powder consisted of zirconia containing 10% by mass of alumina and 1.6 mol% of gadolinium. The crystalline phase of the zirconia in the powder of this example was monoclinic or tetragonal, that is, it consisted of monoclinic and tetragonal phases. Molded bodies and sintered bodies were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was 1400°C.
[0197] Example 7 Except that the calcined powder and alumina powder were mixed with pure water to form a slurry so that the alumina content was 20% by mass, the powder of this example composed of 20% by mass of alumina and 1.6 mol% of gadolinium-containing zirconia was obtained in the same manner as in Example 1. The crystal phase of zirconia in the powder of this example was monoclinic or tetragonal, that is, it consisted of monoclinic and tetragonal. Also, the median diameter was 0.23 μm, the volume particle size distribution curve was a bimodal distribution having peaks at a particle size of 0.14 μm and a particle size of 0.36 μm, and the particle size peak ratio was 1.72. A molded body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was 1450°C.
[0198] Example 8 Except that cerium chloride hexahydrate was added to the zirconia sol aqueous solution after ultrafiltration so that the cerium content was 2.0 mol%, and the calcined powder and alumina sol were mixed with pure water to form a slurry so that the alumina content was 0.25% by mass, the powder of this example composed of 0.25% by mass of alumina and 2.0 mol% of cerium-containing zirconia was obtained in the same manner as in Example 1. The crystal phase of zirconia in the powder of this example was monoclinic or tetragonal, that is, it consisted of monoclinic and tetragonal. Also, the median diameter was 0.17 μm, the volume particle size distribution curve was a bimodal distribution having peaks at a particle size of 0.14 μm and a particle size of 0.34 μm, and the particle size peak ratio was 0.35. A molded body and a sintered body were obtained in the same manner as in Example 1, except that the powder was used.
[0199] Example 9 Except that yttrium chloride hexahydrate was added to the zirconia sol aqueous solution after ultrafiltration so that the yttrium content was 1.6 mol%, and the calcined powder and alumina sol were mixed with pure water to form a slurry so that the alumina content was 0.25% by mass, a powder composed of 0.25% by mass of alumina and 1.6 mol% of yttrium-containing zirconia was obtained in the same manner as in Example 1.
[0200] Also, neodymium hexahydrate was added to the zirconia sol aqueous solution after ultrafiltration so that the neodymium content became 2.0 mol%, and calcined powder and alumina sol were mixed with pure water to form a slurry so that the alumina content became 0.25% by mass. Except for this, powders composed of zirconia containing 0.25% by mass of alumina and 2.0 mol% of neodymium were obtained in the same manner as in Example 1.
[0201] Thereafter, except for mixing the two types of powders obtained above so that the neodymium content became 0.5 mol% and the yttrium content became 1.2 mol%, powders of this Example composed of zirconia containing 0.25% by mass of alumina, 0.5 mol% of neodymium and 1.2 mol% of yttrium were obtained in the same manner as in Example 1. The crystal phase of zirconia in the powder of this Example consisted of monoclinic and tetragonal crystals. Molded bodies and sintered bodies were obtained in the same manner as in Example 1, except that the powder was used.
[0202] Example 10 Neodymium hexahydrate was added to the zirconia sol aqueous solution after ultrafiltration so that the neodymium content became 2.4 mol%, and calcined powder and alumina sol were mixed with pure water to form a slurry so that the alumina content became 0.25% by mass. Except for this, powders composed of zirconia containing 0.25% by mass of alumina and 2.4 mol% of neodymium were obtained in the same manner as in Example 1. The powder was mixed with a powder composed of zirconia containing 0.25% by mass of alumina and 1.6 mol% of yttrium obtained in the same manner as in Example 9 to obtain a powder of this Example composed of zirconia containing 0.25% by mass of alumina, 1.8 mol% of neodymium and 0.4 mol% of yttrium. The crystal phase of zirconia in the powder of this Example consisted of monoclinic and tetragonal crystals. Molded bodies and sintered bodies were obtained in the same manner as in Example 9, except that the powder was used and the sintering temperature was set to 1300 °C.
[0203] Comparative Example 1 An aqueous solution of zirconium oxychloride with zirconium concentration and chloride ion concentration of 0.6 mol / L each was hydrolyzed. The aqueous solution after hydrolysis was ultrafiltered using an ultrafiltration membrane (molecular weight cutoff: 6000) to obtain a zirconia sol with an average sol particle size of 100 nm. zr The concentration was below the detection limit (0.01% by mass or less). After ultrafiltration, yttrium chloride hexahydrate was mixed with the zirconia sol aqueous solution to a yttrium content of 2.0 mol%, and then coprecipitation was performed by adding an aqueous ammonia solution to obtain a precipitate. The obtained precipitate was washed with pure water and dried in an air atmosphere, and then calcined in an air atmosphere at a calcination temperature of 1000°C for 2 hours to obtain a calcined powder.
[0204] The calcined powder was mixed with pure water to form a slurry, which was then ground for 24 hours in a ball mill using 10 mm diameter zirconia balls as the grinding medium. After grinding, the slurry was dried in an air atmosphere at 110°C, and coarse particles with an aggregate diameter exceeding 180 μm were removed by sieving to obtain a powder consisting of zirconia containing 2.0 mol% yttrium, which was used as the powder for this comparative example. The zirconia crystal phase in the powder for this comparative example was monoclinic or tetragonal, i.e., it consisted of monoclinic and tetragonal phases. The powder for this comparative example was subjected to uniaxial compression molding at a pressure of 50 MPa and CIP treatment at a pressure of 196 MPa to obtain molded bodies. The obtained molded bodies were subjected to atmospheric pressure sintering in an air atmosphere at a sintering temperature of 1450°C for 2 hours to obtain sintered bodies.
[0205] Comparative Example 2 A comparative example powder was obtained in the same manner as in Comparative Example 1, except that cerium chloride heptahydrate and yttrium chloride hexahydrate were mixed with an ultrafiltration-removed zirconia sol aqueous solution so that the cerium content was 4.0 mol% and the yttrium content was 1.0 mol%. The zirconia crystal phase in the comparative example powder was monoclinic or tetragonal, i.e., it consisted of monoclinic and tetragonal phases. Molded bodies and sintered bodies were obtained in the same manner as in Example 1, except that this powder was used and the sintering temperature was 1450°C.
[0206] Comparative Example 3 The powder of this comparative example was obtained in the same manner as in Comparative Example 1, except that gadolinium chloride hexahydrate and yttrium chloride hexahydrate were mixed with the ultrafiltration-removed zirconia sol aqueous solution so that the gadolinium content was 0.5 mol% and the yttrium content was 1.5 mol%. The zirconia crystal phase in the powder of this example consisted of monoclinic and tetragonal phases. Molded bodies and sintered bodies were obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was 1650°C.
[0207] Table 1 shows the evaluation results of the powders of the examples and comparative examples, and Table 2 shows the evaluation results of the sintered bodies.
[0208] [Table 1]
[0209] In the table above, a "-" in the columns for stabilizing element content and additives indicates that the stabilizing element and additive are not present.
[0210] [Table 2]
[0211] In the table above, the "Formation of Impact Mark" column is marked with "○" for those in which an impact mark was observed after the ball drop test, and with "×" for those in which no impact mark was observed. For the pattern around the indentation after the Vickers hardness test, "Present" is used for those in which a pattern was observed, "Absent" for those in which no pattern was observed, and "-" for those that were not observed. Figure 7 shows the appearance of the sintered body of Example 8 after the ball drop test. From Figure 7, it can be seen that the area in contact with the dropped weight during the ball drop test formed an impact mark (recess) without fracture such as cracks, that is, the impact mark (recess) as a trace of plastic deformation can be visually confirmed.
[0212] In all of the sintered bodies of Examples 1 to 10, impact marks indicating plastic deformation could be visually confirmed, and the fracture energy of the falling ball was 1.0 J or greater. These sintered bodies could be visually confirmed to have impact marks indicating plastic deformation, similar to those shown in Figure 7.
[0213] All of the sintered bodies in Examples 1 to 10 had a relative density of 98% or more when sintered at a temperature of 1350°C to 1450°C.
[0214] The sintered bodies of Examples 1 to 10 exhibit higher fracture toughness and falling ball fracture energy compared to the sintered body of Comparative Example 1, which contains only yttrium as a stabilizing element. Furthermore, the flexural strength of the sintered bodies of Examples 1 to 10 is 900 MPa or higher, which is higher than that of the sintered body of Comparative Example 2, which contains cerium as a stabilizing element and has a large total amount of stabilizing elements, and the sintered body of Comparative Example 3, which has an average crystal grain size exceeding 1.5 μm.
[0215] Based on the above, it was confirmed that the sintered body of the example possesses high fracture strength, fracture toughness, and excellent impact resistance.
[0216] Figure 8 shows the appearance near the Vickers indentation of Example 4. From Figure 8, it can be confirmed that a unique pattern is formed around the Vickers indentation in Example 4. Similar patterns to those in Figure 8 were also observed in the sintered bodies of Examples 1 to 4 and Examples 8 to 10. Figure 9 shows the results of micro-Raman line measurement near the Vickers indentation in the sintered body of Example 4. From Figure 9, it can be confirmed that monoclinic crystals are formed along the pattern around the Vickers indentation. In the sintered body of Example 4, it is thought that a phase transformation from tetragonal to monoclinic crystals occurred at the periphery of the load application point when a load was applied to the sintered body from the Vickers indenter.
[0217] (Addition of niobium oxide or germanium oxide) Example 11 A powder of this example consisting of zirconia containing 0.05% by mass of niobium oxide (Nb₂O₅) and 2.0 mol% of gadolinium was obtained in the same manner as in Example 3, except that 0.05% by mass of niobium oxide was added instead of alumina sol. The crystal phase of zirconia in the powder of this example consisted of monoclinic and tetragonal crystals. A molded body and a sintered body were obtained in the same manner as in Example 3, except that the powder was used.
[0218] Example 12 A powder of this example consisting of zirconia containing 0.5% by mass of niobium oxide (Nb₂O₅) and 2.0 mol% of gadolinium was obtained in the same manner as in Example 11, except that 0.5% by mass of niobium oxide was added. The crystal phase of zirconia in the powder of this example consisted of monoclinic and tetragonal crystals. A molded body and a sintered body were obtained in the same manner as in Example 11, except that the powder was used and the sintering temperature was set to 1400 °C.
[0219] Example 13 A powder of this example consisting of zirconia containing 0.25% by mass of alumina, 0.25% by mass of germanium oxide (GeO₂), 1.8 mol% of neodymium and 0.4 mol% of yttrium was obtained in the same manner as in Example 10, except that 0.25% by mass of germanium oxide was added in addition to alumina during pulverization. The crystal phase of zirconia in the powder of this example consisted of monoclinic and tetragonal crystals. A molded body and a sintered body were obtained in the same manner as in Example 3, except that the powder was used and the sintering temperature was set to 1300 °C.
[0220] Example 14 The powder of this example was obtained in the same manner as in Example 1, except that neodymium chloride hexahydrate was added to the ultrafiltration-resolved zirconia sol aqueous solution so that the neodymium content was 2.0 mol%, and a mixed powder of calcined powder and germanium oxide was ball-milled so that the germanium oxide content was 0.5 mass%. The zirconia crystal phase in the powder of this example consisted of monoclinic and tetragonal phases. Molded bodies and sintered bodies were obtained in the same manner as in Example 11, except that the powder was used and the sintering temperature was 1250°C.
[0221] Table 3 shows the evaluation results for the powders of these examples, and Table 4 shows the evaluation results for the sintered bodies.
[0222] [Table 3]
[0223] [Table 4]
[0224] From the table above, it can be seen that by adding Nb2O5 instead of alumina as an additive, the bending strength, i.e., static strength of the sintered body improved in Example 11, where the amount of additive was small, and the fracture toughness of the sintered body improved in Example 12, where the amount of additive was large. Furthermore, it can be seen that the bending strength of the sintered body also improved when GeO2 was added as an additive. In addition, it can be seen that there was almost no change in the color of the sintered body compared to the case without any additives. (Addition of pigment components) Example 15 An aqueous solution of zirconium oxychloride with zirconium concentration and chloride ion concentration of 0.6 mol / L each was hydrolyzed. The aqueous solution after hydrolysis was ultrafiltered using an ultrafiltration membrane (molecular weight cutoff: 6000) to obtain a zirconia sol with an average sol particle size of 100 nm. zrThe levels were below the detection limit (0.01 mass% or less).
[0225] To the ultrafiltration-removed zirconia sol aqueous solution, gadolinium chloride hexahydrate and yttrium chloride hexahydrate were mixed to achieve a gadolinium content of 1.4 mol% and a yttrium concentration of 0.4 mol%. After mixing, an aqueous ammonia solution was added, and coprecipitation was carried out to obtain a precipitate. The obtained precipitate was washed with pure water and dried in an air atmosphere, and then calcined in an air atmosphere at a calcination temperature of 1150°C for 2 hours to obtain a calcined powder.
[0226] The calcined powder was mixed with pure water to form a slurry. Then, iron oxide (Fe2O3) was added to the calcined powder so that the Fe2O3 concentration was 0.1% by mass. The mixture was then ground and mixed for 24 hours in a ball mill using 2 mm diameter zirconia balls as the grinding medium. After grinding and mixing, the slurry was dried in an air atmosphere at 110°C, and coarse particles with an aggregate diameter exceeding 180 μm were removed by sieving to obtain the powder of this example, which consists of gadolinia and yttria-containing zirconia containing 0.1% by mass of iron oxide, 1.4 mol% of gadolinium, and 0.4 mol% of yttrium. The zirconia crystal phase in the powder of this example consisted of monoclinic and tetragonal phases.
[0227] The powder of this embodiment was subjected to uniaxial compression molding at a pressure of 50 MPa and CIP treatment at a pressure of 196 MPa to obtain molded bodies. The obtained molded bodies were sintered at atmospheric pressure in an air atmosphere at a sintering temperature of 1400°C for 2 hours to obtain sintered bodies.
[0228] Examples 16 and 17 The powders, molded bodies, and sintered bodies of Examples 16 and 17 were prepared using the same method as in Example 15, except that the compositions were as shown in Table 5.
[0229] Example 18 Except for setting the calcination temperature to 1000°C, the calcined powder of this example was obtained in the same manner as in Example 15, with a gadolinium content of 1.4 mol% and a yttrium content of 0.4 mol%. Except for setting the amount of iron oxide added to 1.0 mass%, and adding 10 mass% of alumina in addition to the iron oxide, the powder of this example was obtained in the same manner as in Example 15, with a gadolinium content of 1.4 mol% and a yttrium content of 0.4 mol%, and containing 1.0 mass% of iron oxide and 10 mass% of alumina. The crystalline phase of the zirconia in the powder of this example consisted of monoclinic and tetragonal phases.
[0230] Examples 19 to 21 Powders for Examples 19 to 21 were prepared in the same manner as in Example 15, except that the composition was as shown in Table 5. The zirconia crystal phases in the powders of these examples consisted of monoclinic and tetragonal phases. Molded bodies and sintered bodies were obtained in the same manner as in Example 15, except that the powder was used and the sintering temperature was 1650°C.
[0231] Examples 22 to 25 Powders for Examples 22 to 25 were prepared in the same manner as in Example 15, except that the same calcined powder as in Example 1 was used and the composition was as shown in Table 5. The zirconia crystal phases in the powders of these examples consisted of monoclinic and tetragonal phases. Molded bodies and sintered bodies were obtained in the same manner as in Example 15, except that the powder was used and the sintering temperature was as shown in Table 6.
[0232] Table 5 shows the evaluation results for the powders of these examples, and Table 6 shows the evaluation results for the sintered bodies.
[0233] [Table 5]
[0234] [Table 6]
[0235] From the table above, it was confirmed that the sintered bodies of Examples 15 to 25 exhibited a color tone different from white due to the addition of pigment components. Furthermore, impact marks, which are traces of plastic deformation, could be observed in the sintered bodies of Examples 15 to 25, and their bending strength was also high at 950 MPa or more, confirming that both their dynamic and static strengths were high. [Explanation of Symbols]
[0236] 100: External view showing an overview of the ball drop test. 101: Sintered body 102: Punching die 103a, 103b: Guide 104: Falling weight 105: Fixing tape 106: Sample stage of the ball-falling test machine 107: Protective tape 200: Sintered body of this embodiment after ball drop test 201: Sintered body 202: Impact mark (indentation) 203: Depth of impact marks (indentations) 300: Conventional sintered body after ball drop test 301: Sintered body 302: Defect (crack) 400: Diagram showing the state of the sintered body being placed on the sample stage of the ball-falling test machine. 401: Sintered body 402: Fixing tape 403: Sample stand for the ball-falling test machine 404: Double-sided tape (protective tape) 500: Diagram showing the method for measuring impact mark depth. 501: Sintered body 502: Impact mark (indentation) 503A,B: Line Profile 504: Depth of impact marks 601: Sintered body in a divided state 602: Defect (crack) 702: Impact mark (indentation) 803: Vickers impression
Claims
1. A sintered zirconia body containing a stabilizing element, wherein the stabilizing element is at least one rare earth element selected from the group consisting of gadolinium and samarium, the content of the stabilizing element is 0.1 mol% or more and less than 3.0 mol%, the average crystal grain size is 0.05 μm or more and 0.75 μm or less, and the body has a region that undergoes plastic deformation.
2. The sintered body according to claim 1, wherein the content of the stabilizing element is 0.1 mol% or more and 2.0 mol% or less.
3. The sintered body according to claim 1 or 2, wherein the rare earth element comprises gadolinium.
4. The sintered body according to claim 1 or 2, further comprising yttrium as the stabilizing element.
5. The sintered body according to claim 4, wherein the yttrium content is 1.2 mol% or less.
6. A sintered body according to claim 1 or 2, comprising alumina.
7. The sintered body according to claim 6, wherein the alumina content is 0.1% by mass or more and 30% by mass or less.
8. Zirconia powder containing a stabilizing element and zirconia with a monoclinic crystallinity exceeding 70%, wherein the stabilizing element contains at least one rare earth element selected from the group consisting of gadolinium and samarium, and the content of the stabilizing element is 0.1 mol% or more and less than 3.0 mol%.
9. The powder according to claim 8, wherein the content of the stabilizing element is 0.1 mol% or more and 2.0 mol% or less.
10. The powder according to claim 8 or 9, wherein the rare earth element comprises gadolinium.
11. The powder according to claim 8 or 9, further comprising the stabilizing element yttrium.
12. The powder according to claim 11, wherein the yttrium content is 1.2 mol% or less.
13. The powder according to claim 8 or 9, wherein the crystallite size of the monoclinic zirconia is greater than 15 nm and less than or equal to 80 nm.
14. BET specific surface area 8m 2 / g or more 40m 2 The zirconia powder according to claim 8 or 9, which is less than / g.
15. The powder according to claim 8 or 9, comprising alumina.
16. The powder according to claim 15, wherein the alumina content is 0.1% by mass or more and 30% by mass or less.
17. A method for producing a sintered body by sintering the powder described in claim 8 or 9.
18. A calcined body containing a stabilizing element, comprising zirconia with a monoclinic coefficient exceeding 70%, wherein the stabilizing element comprises at least one rare earth element selected from the group consisting of gadolinium and samarium, and the content of the stabilizing element is 0.1 mol% or more and less than 3.0 mol%.